Modified olefinic copolymer, resin composition, laminated sheet, prepreg, cured product, substrate with cured product and electronic device

Modified olefin copolymers with alicyclic structures and non-conjugated bonds improve the thermal and dielectric performance of resin compositions, addressing the limitations of existing materials in electronic components.

JP2024178296APending Publication Date: 2024-12-24TOYO INK MFG CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024162124
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-02-27
Filing Date
2024-09-19
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Existing resin compositions used in electronic components lack sufficient heat resistance, crack resistance, and dielectric properties, especially under high-frequency signal conditions, necessitating materials with improved thermal stability and reduced dielectric loss.

Method used

Development of modified olefin copolymers with alicyclic skeletons and non-conjugated carbon-carbon unsaturated bonds, combined with curable compounds, to form resin compositions that enhance crosslinking and improve dielectric and thermal properties.

Benefits of technology

The modified olefin copolymers and resin compositions exhibit excellent dielectric properties, heat resistance, and crack resistance after heat cycling, suitable for use in laminated sheets, prepregs, and electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024178296000001_ABST
    Figure 2024178296000001_ABST
Patent Text Reader

Abstract

To provide a modified olefinic copolymer which is excellent in dielectric characteristics and heat resistance, and in crack resistance after a heat cycle test, a resin composition, and a laminated sheet, a prepreg, a cured product, a substrate with a cured product and an electronic device which are formed using the resin composition.SOLUTION: There is provided a modified olefinic copolymer whose main chain contains a structural unit derived from a conjugated diene compound and / or a structural unit derived from an alicyclic or chain non-conjugated olefin compound, wherein the modified olefinic copolymer has a monocyclic structure and / or a polycyclic structure in at least any one of a side group, a side chain and a molecular chain terminal, and any one ring of the ring having the monocyclic structure and / or the ring having the polycyclic structure is at least any one of an alicyclic skeleton composed of a carbon atom and an alicyclic skeleton composed of a carbon atom and a hetero atom, and has a radical reactive non-conjugated carbon-carbon unsaturated bond.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a modified olefin copolymer, a resin composition, a laminate sheet, and a prepreg. Further, a cured product obtained from the resin composition and a cured product formed by curing the resin composition are The present invention relates to a substrate containing a cured product, and an electronic device equipped with the substrate with the cured product. [Background technology]

[0002] 2. Description of the Related Art Resin compositions or cured products of resin compositions are used in various members of electronic components. For example, a resin composition or a cured resin thereof can be used as an interlayer insulating layer between conductor layers of a multilayer printed wiring board. In addition, glass cloth and other materials are used as insulating layers on the conductor layers of printed wiring boards. Prepregs impregnated with a resin composition are used for semiconductor packages. A resin composition having such a property or a cured product thereof is used as a sealing resin.

[0003] As such a resin composition, for example, Patent Document 1 discloses a resin composition having two N-substituted maleimide groups. The above-mentioned maleimide compound (A), polyphenylene ether (B), and styrene-based compound (C) are used. Structural units derived from maleic anhydride and N-substituted maleimide Patent Document 2 discloses a resin composition containing a copolymer (C) having a structural unit. (A) a styrene-based elastomer, (B) a cyclic imide compound having a specific structure, A thermosetting cyclic imide resin composition containing (C) an epoxy resin and (D) a reaction accelerator in a specific proportion. Patent Document 3 discloses a method for producing a hydrogen-bond cross-linking site having a specific structure. and other side chains containing covalent crosslinking sites. Patent Document 4 discloses a method for producing a polymer having a hydrogen-bond crosslinking site with a specific structure. An elastomeric polymer (A) having a side chain (a) and a Tg of 25° C. or less, The side chains contain hydrogen bond crosslinking sites and covalent bond crosslinking sites, and the Tg is 25 At least one elastomeric polymer (B) having a molecular weight of 0.1 to 1.0 μm is selected from the group consisting of elastomeric polymers (B) having a molecular weight of 0.1 to 1.0 μm. An elastomer component, clay, and an α-olefin resin that does not have a chemically bonded crosslinking site A thermoplastic elastomer composition containing a specific proportion of [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2020-169276 A [Patent Document 2] JP 2022-111423 A [Patent Document 3] JP 2006-131663 A [Patent Document 4] International Publication No. 2017 / 047274 Summary of the Invention [Problem to be solved by the invention]

[0005] As electronic devices become more sophisticated, there is an increasing demand for reliability in the electronic components built into the devices. The resin composition and its cured product also have excellent heat resistance and heat cycle resistance. There is a demand for materials that can provide excellent crack resistance after testing. Supports gigahertz frequency bands for signals used on printed wiring boards used in equipment, etc. There is a need for materials with low dielectric constant and low dielectric loss tangent that can be used in a wide range of applications. It is possible to improve crack resistance after heat cycle testing while satisfying both thermal and thermal properties. There is a need for resins and resin compositions which can do this.

[0006] The present disclosure has been made in view of the above background, and provides a heat-resistant insulating material having excellent dielectric properties and heat resistance. Modified olefin copolymer, resin composition, and and a laminate sheet, a prepreg, a cured product, and a substrate with the cured product formed using the resin composition. and electronic devices. [Means for solving the problem]

[0007] As a result of extensive research, the present inventors have found that the problems of the present disclosure can be solved in the following manner. The present disclosure has been completed based on this finding. [1]: The main chain is a structural unit derived from a conjugated diene compound, and / or an alicyclic or linear non-covalent bond. A modified olefin copolymer containing structural units derived from an olefin compound, Monocyclic and / or polycyclic structures in at least one of the side groups, side chains and molecular chain terminals It has a structure, The ring of said monocyclic structure and / or any ring of said polycyclic structure consists of carbon atoms. At least one of an alicyclic skeleton and an alicyclic skeleton consisting of carbon atoms and hetero atoms and a modified olefin-based copolymer that satisfies at least one of the following (i) and (ii): Polymer. (i) The alicyclic skeleton has a radical-reactive non-conjugated carbon-carbon unsaturated bond. (ii) a carbon atom constituting the alicyclic skeleton and a ring constituting the ring bonded to the carbon atom The free carbon atoms are connected to each other by radically reactive non-conjugated carbon-carbon unsaturated bonds. [2]: The polymer according to [1], wherein the main chain has substantially no unsaturated bonds, except at the molecular chain terminals. Modified olefin copolymer. [3]: [1] or [2] containing a structural unit derived from an aromatic vinyl compound in the main chain The modified olefin copolymer described above. [4]: A block of structural units derived from aromatic vinyl compounds and a block of structural units derived from conjugated diene compounds. and a block containing the above structural unit. system copolymer. [5]: The block containing the structural unit derived from the conjugated diene compound further contains an aromatic vinyl The modified olefin copolymer according to [4], which contains a structural unit derived from a compound. [6]: A hydrogenated styrene-based elastomer. Styrene-ethylene-butylene block copolymer (SEB), Styrene-ethylene-butylene block copolymer Styrene-ethylene-butylene-styrene block copolymer (SEP), Styrene-ethylene-propylene-styrene block copolymer (SEBS), styrene-ethylene-propylene-styrene block copolymer (SEPS), styrene-ethylene-butylene-styrene-styrene block copolymer ( SEBSS), styrene-isobutylene-styrene block copolymer (SIBS), and and styrene-ethylene-ethylene-propylene-styrene block copolymer (SEEPS) The modified olefin copolymer according to any one of [1] to [5], . [7]: A resin composition comprising the modified olefin copolymer according to any one of [1] to [6]. thing. [8]: Further comprising a curable compound, the curable compound being an epoxy compound (b1), Cyanate ester compound (b2), maleimide compound (b3), allyl group-containing compound ( b4), vinyl group-containing compounds (b5) and (meth)acrylate group-containing compounds (b6) and benzoxazine compound (b7) according to [7]. Resin composition. [9]: The resin composition according to [7] or [8], further comprising an inorganic filler.

[10] : A substrate and a resin according to any one of [7] to [9] formed on the substrate. and a resin composition layer formed using the composition.

[11] : A prepreg in which a substrate is impregnated with the resin composition according to any one of [7] to [9]. Gug.

[12] : A cured product obtained from the resin composition according to any one of [7] to [9].

[13] : A cured product formed by curing the resin composition according to any one of [7] to [9]. A substrate with a cured product.

[14] : An electronic device equipped with a substrate with the cured product described in

[13] . Effect of the Invention

[0008] According to the present disclosure, the dielectric properties and heat resistance are excellent, and cracks after heat cycle testing are also reduced. Modified olefin copolymer with excellent durability, resin composition, and molded product using said resin composition The present invention provides a laminate sheet, a prepreg, a cured product, a substrate with the cured product, and an electronic device. This has an excellent effect. [Brief description of the drawings]

[0009] [Figure 1] IR spectra of Resin R-5, Synthesis Example 5, and Comparative Synthesis Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present disclosure will be described in detail below. However, other embodiments may be used as long as they are consistent with the spirit of the present disclosure. The embodiments are also included in the scope of the present disclosure. The range includes the numbers before and after "~" as the lower and upper limits. In this specification, the terms "film" and "sheet" are synonymous and are not differentiated by thickness. In addition, unless otherwise noted, each of the various components appearing in this specification is independently represented by one kind alone. The numerical values ​​described in this specification are based on the numerical values ​​described in the Examples below. This refers to the value obtained by the method.

[0011] 1. Modified olefin copolymer The modified olefin copolymer of the present disclosure (hereinafter also referred to as the present copolymer) has a main chain of conjugated diolefins. Structural units derived from ene compounds and / or alicyclic or linear non-conjugated olefin compounds From the viewpoint of further improving the dielectric properties and heat resistance, the main chain contains a structural unit. It is preferable that the copolymer does not substantially have unsaturated bonds, except for the molecular chain terminals. "Qualitatively free" means that there are no unsaturated bonds other than those that are unavoidably included. At least one of the side groups, side chains and molecular chain ends of the copolymer has a monocyclic structure and and / or polycyclic structures. And, any of the rings of this monocyclic structure and / or polycyclic structure One of the rings is an alicyclic skeleton consisting of carbon atoms and an alicyclic skeleton consisting of carbon atoms and heteroatoms. At least one of the above cases and at least one of the following (i) and (ii): The skeleton refers to a structure formed by atoms that directly form a ring. For example, For example, in the case of a cycloalkenyl group, the atoms directly forming the ring are carbon atoms and do not include hydrogen. In the case of a maleimide group, the atoms directly forming the ring are carbon atoms and heteroatoms (nitrogen). elementary atoms). (i) The alicyclic skeleton has a radical-reactive non-conjugated carbon-carbon unsaturated bond. (ii) a carbon atom constituting the alicyclic skeleton and a ring constituting the ring bonded to the carbon atom The free carbon atoms are connected to each other by radically reactive non-conjugated carbon-carbon unsaturated bonds.

[0012] The "structural unit derived from an alicyclic or linear non-conjugated olefin compound" in the aforementioned main chain is The main chain is made up of aliphatic hydrocarbons that do not have aromaticity (i.e., π-electron conjugation). The copolymer having a structural unit derived from an alicyclic non-conjugated olefin compound has the following structure: It has a ring structure in the main chain. The main chain is the linear trunk of the polymer that constitutes the resin. It is a molecular chain, a chain of carbon atoms. The main chain has an alicyclic structure made of hydrocarbons. From the viewpoint of dielectric properties, it is preferable to have a ring containing a heteroatom in the main chain. Copolymers having a ring derived from a maleimide group, for example, are not included in the present copolymer. From the viewpoint of crack resistance after a heat cycle test, the copolymer is preferably The main chain skeleton is more preferably a chain structure rather than an alicyclic structure.

[0013] "Alicyclic skeleton" in the monocyclic structure and / or polycyclic structure of the side chain, side group or molecular chain terminal " is an aliphatic hydrocarbon group that does not have aromaticity (i.e., a π-electron conjugated system), for example, a cyclic aliphatic hydrocarbon group. The monocyclic and / or polycyclic structures include maleimide groups, carbonyl groups, etc. The term "monocyclic structure" refers to a ring structure having a single ring. A "polycyclic structure" refers to a structure having one or more monocyclic rings. A "polycyclic structure" refers to a bridged structure (bridgehead structure). ), a fused ring structure formed by two or more single rings sharing one edge of each ring (condensation) It is sufficient that the structure has a ring with an alicyclic skeleton. Aromatic rings may be included in a part of the monocyclic structure or a part of the polycyclic structure. It is preferable that there is no.

[0014] What is meant by "radical reactive non-conjugated carbon-carbon unsaturated bond" in (i) and (ii)? , by radical reaction, other modified olefin copolymers and / or curable compounds are covalently Radical reactions are induced, for example, by heating, light irradiation, or electron beam irradiation. will be done.

[0015] Since the copolymer has the above-mentioned structure, it has excellent heat resistance. The main reason for this is that the side groups, The compound has the alicyclic skeleton in at least one of the side chain and the molecular chain terminal, and is non-radical reactive. The conjugated carbon-carbon unsaturated bonds form a cross-linked structure during curing. In particular, the side chain and / or side group are The presence of this alicyclic skeleton suppresses steric hindrance, improving reactivity and enhancing curability. It is possible.

[0016] Furthermore, the cured product of the resin composition containing the copolymer has excellent dielectric properties. The main reason for this is At least one of a side group, a side chain and a molecular chain end has the alicyclic skeleton, and a conjugated dicyclic Structural units derived from ene compounds and / or structural units derived from alicyclic or linear non-conjugated olefin compounds By including structural units, it is possible to crosslink the polymer through oxygen or nitrogen atoms (e.g. (Compared to curing using epoxy compounds), the crosslinking site is a carbon-carbon bond. This is thought to be due to the fact that the polarization is reduced and dielectric relaxation is suppressed. Since the alicyclic skeleton is present in the cyclic and / or side groups, there is little steric hindrance and the reaction is highly reactive, making it hard and flexible. This reduces the amount of non-conjugated carbon-carbon unsaturated bonds remaining after the oxidation reaction. The generation of acid groups and the associated deterioration of dielectric properties can be suppressed.

[0017] In addition, since the cured product of the resin composition containing the present copolymer has the above-mentioned structure, The main reason for this is that the main chain is made of a conjugated diene compound. The flexibility is improved by using conventional structural units and / or alicyclic or linear non-conjugated olefinic skeletons. While increasing the molecular weight of the compound, the carbon of the alicyclic skeleton of the compound in at least one of the side group, the side chain, and the molecular chain end is This is believed to be due to the structure that creates a cross-linked structure through -carbon unsaturated bonds. From the viewpoint of effectively improving the performance, a conjugated diene compound having substantially no unsaturated bond in the main chain is preferably used. It is preferred that the main chain skeleton is a structural unit and / or an alicyclic or linear non-conjugated olefin skeleton. I wish.

[0018] 1-1. Main chain structure The copolymer has a main chain that is made of a structural unit derived from a conjugated diene compound and / or an alicyclic or linear Contains structural units derived from non-conjugated olefin compounds. Improves dielectric properties and heat resistance. From the viewpoint of the above, it is preferable that the main chain has substantially no unsaturated bonds except at the molecular chain terminals. In this case, if unsaturated bonds remain in the main chain, hydrogenation reaction By the reaction (hydrogenation reaction), a copolymer having substantially no unsaturated bonds is obtained.

[0019] The monomers used to obtain the structural units derived from the conjugated diene compound that constitute the main chain of this copolymer (hereinafter The monomer A may be selected from known monomers. A suitable example is butadiene. , isoprene, 2,3-dimethyl-butadiene, 2-phenyl-butadiene, 1,3-phenyl Pentadiene, 2-methyl-1,3-pentadiene, 1,3-hexadiene, 1,3-octane 1,3-cyclohexadiene, 2-methyl-1,3-octadiene, 1,3, These include 7-octatriene, myrcene, farnesene, chloroprene and mixtures thereof. Among these, butadiene and isoprene are more preferable.

[0020] The main chain of the copolymer is constituted by a structural unit derived from an alicyclic or linear non-conjugated olefin compound. The monomer to be obtained (hereinafter also referred to as monomer B) can be appropriately selected from known monomers. Examples include ethylene, propylene, 1-pentene, 1-hexene, 1-heptene, and 1-octene. α-olefins such as methacrylate, heteroatom-substituted alkene compounds such as N-vinylpyrrolidone, Bicyclic rings such as norbornene and norbornadiene, dicyclopentadiene and dihydrodicyclo Tricyclic rings such as pentadiene, tetracyclic rings such as tetracyclododecene, tricyclopentadiene, etc. norbornene-based compounds such as five-ring compounds, tetracyclopentadiene and other seven-ring compounds, and their derivatives Among these, ethylene and propylene are preferred, and ethylene is particularly preferred. Preferred.

[0021] In order to provide excellent mechanical strength and heat resistance, the copolymer contains an aromatic ring in the main chain. It is preferable that the copolymer has a structural unit derived from a vinyl compound. The monomer for obtaining the structural unit derived from an aromatic vinyl compound (hereinafter also referred to as monomer C) is a known Suitable examples include styrene, α-methylstyrene, and o-methylstyrene. Methylstyrenes such as styrene, m-methylstyrene, and p-methylstyrene; 2,6-di Methylstyrene, 2,4-dimethylstyrene, α-methyl-o-methylstyrene, α-methyl methyl-m-methylstyrene, α-methyl-p-methylstyrene, β-methyl-o-methylstyrene Styrene, β-methyl-m-methylstyrene, β-methyl-p-methylstyrene, 2,4 ,6-trimethylstyrene, α-methyl-2,6-dimethylstyrene, α-methyl-2, 4-Dimethylstyrene, β-methyl-2,6-dimethylstyrene, β-methyl-2,4- Dimethylstyrene, ot-butylstyrene, mt-butylstyrene, pt-butyl Styrene, o-methoxystyrene, m-methoxystyrene, p-methoxystyrene, Examples include vinylene, vinylnaphthalene, and N-vinylcarbazole. From the viewpoint of the performance, styrene, α-methylstyrene, p-methylstyrene and their mixtures A mixture of these is preferred, and styrene is more preferred.

[0022] The copolymer may be any of the above-mentioned monomers A and B within the scope of the present disclosure. Other monomers copolymerizable with the above (hereinafter also referred to as monomer D) may be used. In order to maintain good crack resistance after heat cycles, the main chain skeleton is It is preferable that the ring structure does not contain a heterocycle. Specific examples of the monomer D include N-vinyl carbamide, Aromatic vinyl compounds such as vinyl benzol, vinyl naphthalene and vinyl anthracene, β-pyridinium Examples include menthene, 8,9-p-menthene, and dipentene.

[0023] The copolymer may be a random copolymer, a block copolymer, or a gradient copolymer. However, from the viewpoint of achieving both heat resistance and stress relaxation, block copolymers are preferred. From the viewpoint of achieving both heat resistance and stress relaxation, a block copolymer having structural units derived from aromatic vinyl compounds is used. Examples of the block copolymer include a block copolymer containing a structural unit derived from a conjugated diene compound and a structural unit derived from a conjugated diene compound. From the viewpoint of achieving both heat resistance and stress relaxation, the block copolymer is a copolymer made of constituent units derived from conjugated diene compounds. It is more preferable that the block containing the unit contains a structural unit derived from an aromatic vinyl compound at both ends. The main chain of this copolymer is composed of blocks of structural units derived from aromatic vinyl compounds. and a block containing a structural unit derived from a conjugated diene compound. It is preferable that the ABA type trialkylamine contains structural units derived from butadiene and isoprene. Block copolymers, AB type diblock copolymers are preferred, ABA type triblock copolymers are preferred. A copolymer is more preferable. A preferred example of the block A is a styrene-based monomer or a block Examples of B include monomers derived from butadiene and isoprene.

[0024] A preferred example of the copolymer is a hydrogenated styrene-based elastomer, styrene-ethylene Butylene block copolymer (SEB), styrene-ethylene-propylene block copolymer Polymer (SEP), Styrene-Ethylene-Butylene-Styrene Block Copolymer (SEBS) ), styrene-ethylene-propylene-styrene block copolymer (SEPS), styrene Styrene-ethylene-butylene-styrene-styrene block copolymer (SEBSS), Styrene-isobutylene-styrene block copolymer (SIBS), styrene-ethylene-ethylene Examples include modified styrene-propylene-styrene block copolymers (SEEPS). Cut.

[0025] The monomers A to D may each be used independently as one type alone or as two or more types. The total of structural units derived from monomer A and structural units derived from monomer B that constitute the copolymer (either From the viewpoint of stress relaxation, the copolymer 100% by mass is The content is preferably 30 to 90 mass %, and more preferably 40 to 80 mass %. The content of the monomer C constituting the present copolymer is preferably 55 to 75 mass %. From the viewpoint of heat resistance, the content of the structural unit is 10 to 70% by mass in the copolymer (100% by mass). It is preferable that the content is 15 to 60 mass%, more preferably 20 to 45 mass%. It is more preferable that the content of the copolymer is 25 to 45 mass %, particularly preferably 25 to 45 mass %. The total of the structural units derived from the monomers A to C constituting the copolymer is 90% by mass or more in 100% by mass of the copolymer. It is preferable that the content of the fluorine-containing compound is 95% by mass or more, and more preferably 100% by mass or more. The above ranges are based on mass % of the olefin copolymer before modification.

[0026] 1-2. Side groups, side chains and molecular chain ends The copolymer has at least one of a side group, a side chain, and a molecular chain end, and (i) and (i i) A monocyclic structure and / or a polycyclic structure having an alicyclic skeleton that satisfies at least one of the following conditions: This structure (hereinafter also referred to as a non-conjugated C=C bond-containing ring) allows the copolymer to be crosslinked. By crosslinking this copolymer, it is possible to impart excellent heat resistance and heat resistance. It improves crack resistance after cycle testing.

[0027] As a monocyclic structure or polycyclic structure having an alicyclic skeleton satisfying the above (i), the following chemical formula (1 ) are mentioned. [ka] R in the formula1 is a direct bond or a methylene group, and R 2 is hydrogen or a methyl group. The * in the figure indicates the bonding site with the main chain or side chain of the modified olefin copolymer. The hydrogen atom to be bonded may be substituted with a substituent. Such a substituent may be a group having a carbon number of 1 to 18 alkyl groups (methyl, ethyl, isopropyl, t-butyl, etc.), carbon Alkoxy groups having 1 to 18 carbon atoms (e.g., methoxy, ethoxy, propoxy, etc.), aryl groups ( phenyl group, naphthyl group, etc.), heteroaromatic group (thienyl group, etc.), haloaryl group (penta Fluorophenyl group, 3-fluorophenyl group, 3,4,5-trifluorophenyl group, etc. ), alkenyl groups such as vinylidene groups, alkynyl groups, amide groups, acyl groups, haloalkynyl groups, (perfluoroalkyl groups, etc.), hydroxyl groups, nitro groups, cyano groups, carboxy groups and halogen groups (such as a fluoro group, a chloro group, and a bromo group).

[0028] A specific example of the above (ii) is a group represented by the following chemical formula (2). [ka] R in the formula 1 , R 2 The * in the formula is as explained in chemical formula (1). The hydrogen atom bonded to may be substituted with a substituent, and preferred examples of such a substituent include Examples of the substituents include those exemplified in chemical formula (1).

[0029] From the viewpoint of dielectric properties, a radiator that satisfies at least one of the above (i) and (ii) is The alicyclic skeleton has a non-conjugated carbon-carbon unsaturated bond that is reactive to carbon atoms, and the maleimide group or other aryl groups are attached to the alicyclic skeleton. It is preferable that the compound does not contain a heteroatom. From the viewpoint of dielectric properties, the compound does not contain a non-conjugated carbon-carbon unsaturated bond. Suitable examples of alicyclic skeletons having the above structure include norbornene, terpenes (e.g., α-pinene and rimono). If a norbornene group is included, the alicyclic structure does not contain a heteroatom. This improves the dielectric properties.

[0030] Substantially all of the molecular chain terminals of the present copolymer may have a structure having the present alicyclic skeleton. In addition, a part of the molecular chain terminals may contain a functional group other than the alicyclic skeleton. A part of the molecular chain ends may be blocked ends having no functional group. The copolymer does not have an alicyclic skeleton, but the copolymer may have an alicyclic skeleton in its side chain and / or side group. The alicyclic skeleton may be present at least in one of the molecular chain terminal, the side chain, and the side group. Good.

[0031] 1-3. Copolymerization format, weight average molecular weight, etc. This copolymer has excellent heat resistance and crack resistance after heat cycle testing. A preferred example is a block copolymer consisting of structural units derived from an aromatic vinyl compound. Examples of block copolymers include a block copolymer containing a block having a structural unit derived from a conjugated diene compound and a block having a structural unit derived from a conjugated diene compound. In addition, the block containing the structural unit derived from the conjugated diene compound may further contain an aromatic vinyl. Modified block copolymers containing structural units derived from compounds are also suitable.

[0032] The weight average molecular weight (hereinafter, also referred to as Mw) of the copolymer is not particularly limited. From the viewpoint of improving the crack resistance after the cycle test, Mw is set to 20,000 or more. It is preferable that the number of the ions is 50,000 or more, more preferable that the number of the ions is 70,000 or more. From the viewpoint of compatibility between the present copolymer and the curable compound, it is more preferable that the present copolymer is The Mw of the polymer is preferably 400,000 or less, more preferably 300,000 or less, and more preferably 200 ,000 or less is even more preferable.

[0033] The position of the non-conjugated C=C bond-containing ring of this copolymer is either a side group, a side chain, or a molecular chain end. However, from the viewpoint of the manufacturing process, a side group or a side chain is preferable. The amount of the non-conjugated carbon-carbon unsaturated bonds having a high reactivity is not particularly limited, but it is preferable to use a compound having a high heat resistance. From the viewpoint of (i) and (ii), the radical reactive non-conjugated carbon-carbon unsaturated The bond valence is preferably 1 to 50 mgKOH / g, more preferably 2 to 35 mgKOH / g, 5 to 25 mgKOH / g is more preferable.

[0034] The content of blocks consisting of structural units derived from aromatic vinyl compounds improves heat resistance and heat cycle. From the viewpoint of crack resistance after crack testing, 10 to 70% by mass of this copolymer is used. It is preferable that the content is 20 to 60 mass %, more preferably 20 to 60 mass %, and further preferably The content is 25 to 45% by mass.

[0035] 1-4. Manufacturing method An example of a method for producing the present copolymer will be described. At least one of a conjugated diene compound and an alicyclic or linear non-conjugated olefin compound is included. The unmodified resin (unmodified copolymer) is obtained by polymerizing the monomers containing the olefin. Any of radical polymerization, anionic polymerization, cationic polymerization, and living polymerization may be used. The unmodified block copolymer can be obtained by sequential addition of the monomers. In the case where the unmodified block copolymer is made to have substantially no unsaturated double bonds in the main chain, After polymerization, the copolymer can be hydrogenated by a known method such as reacting it with pressurized hydrogen in the presence of a catalyst. good.

[0036] A non-conjugated C=C bond-containing ring is introduced into at least one of the side chains, side groups, and molecular chain ends (modification). The method for introducing a non-conjugated C=C bond-containing ring into the unmodified copolymer is to react the unmodified copolymer with a compound capable of introducing a non-conjugated C=C bond-containing ring into the unmodified copolymer. A method of producing the polyolefin copolymer through a reaction step of polymerizing the olefin copolymer is preferable. In this case, by using a monomer having this non-conjugated C=C bond-containing ring in part, it is possible to form a C=C bond in the side group. Copolymers having rings may be obtained.

[0037] The introduction of non-conjugated C=C bond-containing rings into the molecular chain terminals polymerizes unmodified olefin copolymers. Then, if necessary, a hydrogenation reaction is carried out, and a compound having a non-conjugated C=C bond-containing ring is reacted. The compound having a functional group at the molecular chain end of an unmodified olefin copolymer is obtained by the following steps. may be introduced and reacted with a compound having a non-conjugated C=C bond-containing ring. For example, acrylic acid is introduced to the molecular chain end. Then, a functional group that reacts with the carboxyl group (e.g. At least one of (i) and (ii) having a group (e.g., an amino group, an epoxy group, a hydroxy group) Compounds having a monocyclic structure and / or a polycyclic structure with an alicyclic skeleton that satisfies any of the following: By reacting with, a non-conjugated C=C bond-containing ring can be introduced at the molecular chain end.

[0038] The introduction of a non-conjugated C=C bond-containing ring into the side chain of an unmodified olefin copolymer, for example, It can be produced by adding a radical initiator under heating and graft polymerizing an acid anhydride. Examples of compounds capable of introducing an acid anhydride group include maleic anhydride and citraconic anhydride. Examples of the aryl esters include aryl esters and itaconic anhydride. Commercially available products containing these aryl esters may also be used.

[0039] After introducing an acid anhydride into the unmodified olefin copolymer, which is the precursor of this copolymer, An alicyclic compound which satisfies all or part of the anhydride and at least one of (i) and (ii). Reacting the compound having a monocyclic structure and / or a polycyclic structure having the formula This gives the present copolymer having non-conjugated C=C bond-containing rings in the side chains.

[0040] A monocyclic structure having an alicyclic skeleton that satisfies at least one of (i) and (ii). and / or a compound having a polycyclic structure, which has a functional group that reacts with carboxylic acid as a substituent. The following compounds having a functional group (amino group, ethylene group, etc.) that reacts with carboxylic acid are exemplified. Indene rings having a substituent such as an epoxy group or a hydroxy group; alkene ring; 5-methyl-bicyclo[2.2.1]hept-2-ene, 5-ethyl-bicyclo[2.2.1]hept-2-ene Cyclo[2.2.1]hept-2-ene, 5-butyl-bicyclo[2.2.1]hept- 2-ene, 5-hexyl-bicyclo[2.2.1]hept-2-ene, 5-decyl-bicyclo[2.2.1]hept-2-ene Chloro[2.2.1]hept-2-ene, 5-cyclohexyl-bicyclo[2.2.1]hept-2-ene 5-cyclopentyl-bicyclo[2.2.1]hept-2-ene, 5-cyclopentyl-bicyclo[2.2.1]hept-2-ene, etc. 5-Ethylidene-bicyclo[2.2.1]hept-2-ene (5-Ethylidene 5-vinyl-bicyclo[2.2.1]hept-2-ene, 5 -propenyl-bicyclo[2.2.1]hept-2-ene, 5-cyclohexenyl-bicyclo[2.2.1]hept-2-ene Chloro[2.2.1]hept-2-ene, 5-cyclopentenyl-bicyclo[2.2.1] Alkenyl-substituted hept-2-enes; 5-phenyl-bicyclo[2.2.1]hept -2-ene (5-phenyl-2-norbornene), bicyclo[2.2.1]hept-2- ene, tricyclo[4.3.0.12,5]deca-3,7-diene, methyldicyclopentene Dimethyldicyclopentadiene, tetracyclo[9.2.1.02,10.0 3,8]tetradeca-3,5,7,12-tetraene, tetracyclo[10.2.1.0 2,11.04,9]pentadeca-4,6,8,13-tetraene and other norbornenes Examples of rings that include tetracyclododecene, 8-methyltetracyclododecene, 8 -Ethyltetracyclododecene, 8-cyclohexyltetracyclododecene, 8-cyclo Unsubstituted or alkyl-substituted tetracyclododecene such as pentyltetracyclododecene 8-Methylidenetetracyclododecene, 8-Ethylidenetetracyclododecene, 8- Vinyltetracyclododecene, 8-propenyltetracyclododecene, 8-cyclohexene cyclopentenyltetracyclododecene, 8-cyclopentenyltetracyclododecene, etc. Tetracyclododecenes with aromatic rings such as 8-phenyltetracyclododecene Examples of the tetracyclododecenes include those having a functional group (amino group) that reacts with carboxylic acid. 8-Methoxycarbonyl tert-butyl ether having a substituent such as a carboxyl group, an epoxy group, or a hydroxyl group Tetracyclododecene, 8-methyl-8-methoxycarbonyltetracyclododecene, 8- Hydroxymethyltetracyclododecene, 8-carboxytetracyclododecene, tetra Cyclododecene-8,9-dicarboxylic acid, Tetracyclododecene-8,9-dicarboxylic acid Examples include tetracyclododecenes having a substituent containing an oxygen atom, such as an anhydride.

[0041] An alicyclic skeleton having an amino group and satisfying at least one of (i) and (ii). As a compound having a monocyclic structure and / or a polycyclic structure, for example, the following compound ( 3) can be given as an example. [ka] R in the formula 1 , R 2 is as explained in chemical formula (1). 3 is a direct bond or carbon number R is an alkyl group having a length of 1 to 20. 3 is preferably a direct bond or an alkyl group having 1 to 6 carbon atoms. K, R 3 is preferably a direct bond or an alkyl group having 1 to 4 carbon atoms. The hydrogen atom to be bonded may be substituted with a substituent. Such a substituent is, for example, a group represented by the chemical formula: The substituents exemplified in the explanation of (1) are exemplified. Particularly preferred compounds are 5-norborone An example is 2-methylamine.

[0042] After introducing an acid anhydride into an unmodified olefin copolymer, all or a part of the acid anhydride and the a and (ii) having an alicyclic skeleton that satisfies at least one of (i) and (ii) By reacting with a compound having a monocyclic structure and / or a polycyclic structure, an imide This imide bond forms a maleimide compound ( The compatibility with b3) is improved, which increases the crosslinking property and improves the heat resistance of the cured product. From the viewpoint of the heat resistance of the copolymer, it is preferable to use imidazole in either the side chain, side group, or molecular chain end of the copolymer. A resin in which a maleimide bond is introduced and which is combined with a maleimide compound (b3) as a curable compound. The composition is preferred.

[0043] The reaction temperature for introducing acid anhydride groups into unmodified olefin copolymers is 50 to 2 The temperature is preferably 00° C., and more preferably 100 to 180° C. After the acid anhydride is introduced, the alicyclic skeleton is The temperature for reacting with the compound having a monocyclic structure and / or a polycyclic structure is 80 to 2 A temperature of 50°C is preferred, and a temperature of 100 to 200°C is more preferred. The reaction time for introducing acid anhydride groups into unmodified olefin copolymers is 1 to 24 hours. The reaction time is preferably 0 minutes, and more preferably 10 to 180 minutes. The reaction time with the compound having a monocyclic structure and / or a polycyclic structure is 30 to 240 The time is preferably from 10 to 20 minutes, and more preferably from 60 to 180 minutes.

[0044] When an acid anhydride group is introduced and the alicyclic skeleton is introduced into the side chain and / or side group, oxidation prevention is performed. It is preferable to add an antioxidant. As the antioxidant, for example, a known antioxidant can be used. Specific examples of the antioxidant include phenothiazine, bis-(1-dimethylbenzamide), Phenothiazines such as 3,7-dioctylphenothiazine and 3,7-dioctylphenothiazine Compound; Bis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate 2,4-Bis[(laurylthio)methylpropionic acid][ethylenebis(oxyethylene)] 1,3,5-tris(3,5-di-t-butyl-4-hydroxyphenyl)-o-cresol benzyl), 1,3,5-tris(4-t-butyl-3-hydroxy-2,6-dimethyl benzyl), 2,4-bis-(n-octylthio)-6-(4-hydroxy-3,5-di -t-butylanilino)-1,3,5-triazine, and pentaerythritol tetraacetate Kis 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, etc. hindered phenol compounds; phenoxazine compounds such as phenoxazine; 4-diphenyl ether N-nitrosophenol, N-nitrosodiphenylamine, N-nitrosocyclohexylhydrochloride Nitroso compounds such as xylamine and N-nitrosophenylhydroxylamine, Its salts; methylhydroquinone, t-butylhydroquinone, 2,5-di-t-butyl quinone compounds such as 4-hydroquinone and 4-benzoquinone; 4-methoxyphenol, 4 Examples of phenolic compounds include 1-methoxy-1-naphthol and t-butylcatechol. can be done. Among them, as the antioxidant, phenothiazine-based compounds are preferred because they provide a more excellent effect in the present disclosure. a compound selected from the group consisting of a phenol-based compound, a hindered phenol-based compound, and a phenoxazine-based compound; At least one of these is preferred.

[0045] As catalysts, aliphatic tertiary amines such as triethylamine, aromatic amines such as dimethylaniline, etc. aromatic tertiary amines, heterocyclic tertiary amines such as pyridine, picoline, and isoquinoline, etc. Examples of the dehydrating agent include aliphatic acid anhydrides such as acetic anhydride, benzoic anhydride, etc. As the radical initiator, the following compounds are preferred. can be done.

[0046] The organic solvent used in the polymerization is, for example, N-methyl-2-pyrrolidone (NMP), -butanone, dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DM F), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide, hexadecyl dimethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone Examples include dioxane, tetrahydrofuran, diglyme, triglyme, and cresol. Solvents are used alone or in combination. Aromatic solvents such as xylene and toluene are preferred. Aromatic hydrocarbons can also be used in combination.

[0047] 2.Resin composition The resin composition according to the present embodiment (hereinafter also referred to as the present composition) comprises at least the present copolymer. According to the present composition, the non-conjugated C=C bond-containing rings of the present copolymer are radically opened. The composition can be crosslinked by the addition of a curing agent. By including a curable compound, the non-conjugated C=C bond-containing ring of the copolymer and the curable compound can be cured. By including a curable compound, the crosslink density of the cured product can be controlled. This makes it easier to control.

[0048] Since the composition has the above-mentioned structure, the cured product has excellent heat resistance. The main reason is The side groups, side chains and / or molecular chain ends have relatively mild reactivity. The non-conjugated carbon-carbon unsaturated bonds of the alicyclic skeleton, which have high reactivity, or the bonds directly connected to the alicyclic skeleton The cross-linking structure can be constructed starting from the non-conjugated carbon-carbon unsaturated bond, and The relatively flexible and tough chain-like hydrocarbon skeleton of the copolymer reduces the mobility of the copolymer after curing. This is believed to be due to the suppression of the chain structure of the main chain, which improved the stress relaxation and dispersibility. The hydrocarbon skeleton and the relatively low reactive "alicyclic structure-derived radical reactive non-conjugated carbon By combining this copolymer, which has a carbon-carbon unsaturated bond, with a curable compound, crosslinking can be achieved. It is believed that this has improved heat resistance by creating a contrast between the dense and sparse areas of the bridge structure. From the viewpoint of further improving heat resistance, the chain-like hydrocarbon skeleton of the main chain is made to be a saturated hydrocarbon skeleton. It is preferable that

[0049] In addition, since the composition has the above-mentioned structure, it is possible to provide a resin composition having excellent dielectric properties. The alicyclic skeleton is present in at least one of the side group, the side chain, and the molecular chain terminal, and the main chain By using the copolymer having a linear hydrocarbon skeleton, Since it has an alicyclic skeleton, it has little steric hindrance and is highly reactive, so it does not remain after the curing reaction. This reduces the non-conjugated carbon-carbon unsaturated bonds that are generated by oxidation. It is believed that the accompanying deterioration in dielectric properties can be suppressed, resulting in excellent dielectric properties. Each component of the composition and the method for producing it are described in detail below.

[0050] 2-1. Curing compound The curable compound refers to a compound that crosslinks or hardens by heating, light irradiation, electron beam irradiation, etc. The type of the curable compound is not particularly limited. The curable compound may be used alone or in the form of a mixture of the same or different compounds. In any case, two or more types can be combined.

[0051] Suitable examples of the curable compound include epoxy compounds (b1), cyanate ester compounds ( b2), maleimide compounds (b3), allyl group-containing compounds (b4), vinyl group-containing compounds (b5), (meth)acrylate group-containing compounds (b6), benzoxazine compounds (b7 ) can be exemplified (hereinafter, also referred to as components (b1) to (b7)). It is preferable to have one or more selected from the group consisting of (b1) to (b7).

[0052] The curable compound is a curable compound having a radical-reactive non-conjugated carbon-carbon unsaturated bond. It is preferable that the compound contains a radical (B1) (hereinafter, also simply referred to as a curable compound (B1)). A reactive non-conjugated carbon-carbon unsaturated bond is one that reacts with other curing compounds to form a crosslinked structure. and / or reacts with the radically reactive non-conjugated carbon-carbon unsaturated bonds of the copolymer to form bonds The term refers to a bond that can form a radically reactive non-conjugated carbon-carbon unsaturated bond. Suitable examples of the curable compound (B1) include maleimide compounds (b3), allyl group-containing compounds (b4), Compound (b4), vinyl group-containing compound (b5), (meth)acrylate group-containing compound (b 6) are listed.

[0053] From the viewpoint of further improving the heat resistance, a maleimide compound (b3) is used as a curable compound. The maleimide compound (b3) may be used alone or in combination with other maleimide compounds. Combination of substance (b3) with one or more of components (b1), (b2), (b4) to (b7). A preferred combination is a cyanate ester compound (b2) and a maleate. A combination of maleimide compound (b3), a combination of maleimide compound (b3) and components (b4) to (b7), Among these, the maleimide compound (b3) is preferably used in combination with at least one of the maleimide compounds (b1) and (b2). A combination of the maleimide compound (b In the case where 3) is crosslinked by heating and reacting with a benzoxazine compound (b7), This is particularly preferred since it improves the reactivity of maleimide and also provides excellent dielectric properties.

[0054] Maleimide is used to form stronger crosslinks by reactions between carbon-carbon unsaturated bonds. Compound (b3) and allyl group-containing compound (b4), maleimide compound (b3) and vinyl group-containing compound (b5) Compound (b5), maleimide compound (b3) and (meth)acrylate group-containing compound (b6 ) combination is preferred.

[0055] In order to improve toughness, the polyphenylene ether structure is preferably used in (b1) to (b7). It is preferable to use a curable compound having the following structure. More preferably, an allyl group-containing compound ( b4), vinyl group-containing compounds (b5), (meth)acrylate group-containing compounds (b6), and and benzoxazine compound (b7), which has the following general formula (4) as a part of its structure: It is a phenylene ether compound. [ka] R 11 , R 12 , R 13 and R 14 each independently represents a hydrogen atom, Halogen atoms (fluorine atoms, chlorine atoms, bromine atoms, etc.), alkyl groups which may have a substituent methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tetramethyl Straight-chain or branched compounds with 1 to 6 carbon atoms, such as rt-butyl, pentyl, and heptyl groups cyclohexyl group, etc.), alkoxy groups which may have a substituent (methyl group, alkoxy groups having 1 to 6 carbon atoms, such as methoxy, ethoxy, butoxy, and propoxy groups; Optionally substituted aryl groups (phenyl, naphthyl, etc.); Examples of groups which may be substituted include an amino group, a carboxy group, a nitro group, and a cyano group.

[0056] From the viewpoint of heat resistance, especially long-term heat resistance, the average curing functional group of the polyphenylene ether compound The number is preferably 1 to 10, and more preferably 2 or more.

[0057] The Mw of the components (b4) to (b7) having a polyphenylene ether structure is not particularly limited. However, from the viewpoint of improving crack resistance after heat cycle testing, it is preferable that the value is 200 or more. It is preferable that the Mw is 500 or more, and more preferable that the Mw is 500 or more. Considering ease of use, the cost is less than 10,000 yen.

[0058] The composition contains 10 to 9% by mass of the curable compound, based on 100% by mass of the components excluding the filler and the solvent. It is preferable to use 8% by mass, more preferably 30 to 90% by mass, and 45 to 8% by mass is more preferable. It is more preferable to use 5% by mass.

[0059] From the viewpoint of heat resistance, the molecular weight of the curable compound is 100 or more and less than 10,000, and A curable compound (B) having a radical reactive non-conjugated carbon-carbon unsaturated bond In addition to the above-mentioned embodiment, the present copolymer and the curable compound (B1) are preferably used. By making the content of the copolymer 5 to 40% by mass relative to the total of 100% by mass, The heat resistance is improved.

[0060] The molecular weight of the curable compound is the molecular weight of the low molecular weight compound, and is the molecular weight of the monomer. In the case of a compound obtained by polymerization, it refers to the number average molecular weight. In this case, the molecular weight of the curable compound is calculated by multiplying the molecular weight of each curable compound by the molecular weight of that curable compound. The total content (mass%).

[0061] The epoxy compound (b1) refers to a curable compound having an epoxy group. It is preferable to use (b1) in combination with an active ester compound. It has one or more ester groups in one molecule that react with epoxy groups and harden epoxy resins. The active ester compound is commercially available as HPC-80 manufactured by DIC Corporation. 00-65T", "EXB9416-70BK" and "EXB8100-65T" etc. An example can be given.

[0062] By using an active ester compound, the epoxy compound (b1) and the active ester compound can be reacted. The reaction with the compound generates an ester group. This makes it easier to use than when using a phenol-based hardener. As a result, the dielectric properties can be improved more effectively.

[0063] Specific examples of the epoxy compound (b1) include glycidyl ether type epoxy resins; tetraglyceryl ether type epoxy resins; Glycidyl diaminodiphenylmethane, triglycidyl paraaminophenol, triglycidyl glycidyl meta aminophenol, or tetraglycidyl meta xylylene diamine, sorbitol Glycidylamine type epoxy resins such as diglycidyl polyglycidyl ether; diglycidyl phthalate diglycidyl hexahydrophthalate, or diglycidyl tetrahydrophthalate Glycidyl ester type epoxy resins such as epoxycyclohexylmethyl-epoxysilane Cyclohexane carboxylate, or bis(epoxycyclohexyl) adipate, etc. Cycloaliphatic (alicyclic) epoxy resins; bisphenol A type epoxy resins, bisphenol F type epoxy resin, bisphenol S type epoxy resin, bisphenol AD ​​type epoxy resin Examples of epoxy resins include cresol novolac epoxy resins and phenol novolac epoxy resins. Epoxy resin, α-naphthol novolac type epoxy resin, bisphenol A type novolac Epoxy resin, dicyclopentadiene epoxy resin, tetrabromobisphenol Examples include A-type epoxy resins and brominated phenol novolac type epoxy resins.

[0064] The cyanate ester compound (b2) refers to a curable resin having a cyanate group. As the cyanate ester compound (b2), bisphenol A type cyanate ester resin, bisphenol A type cyanate ester resin, Phenol A type cyanate ester, bisphenol F type cyanate ester resin, bisphenol Nol E type cyanate ester resin, Bisphenol S type cyanate ester resin, Bis Phenol sulfide type cyanate ester resin, phenylene ether type cyanate ester ether resin, naphthylene ether type cyanate ester resin, biphenyl type cyanate ester ter resin, tetramethylbiphenyl type cyanate ester resin, polyhydroxynaphthalene Cyanate ester resin, phenol novolac type cyanate ester resin, cresol Novolac type cyanate ester resin, Triphenylmethane type cyanate ester resin Fat, tetraphenylethane type cyanate ester resin, dicyclopentadiene-phenol Addition reaction type cyanate ester resin, phenol aralkyl type cyanate ester resin , naphthol novolac type cyanate ester resin, naphthol aralkyl type cyanate Ester resin, naphthol-phenol co-condensed novolac type cyanate ester resin, naphthol Toluene-cresol co-condensed novolac type cyanate ester resin, aromatic hydrocarbon formaldehyde Aldehyde resin modified phenolic resin type cyanate ester resin, biphenyl modified novolac type cyanate ester resin, anthracene type cyanate ester resin, etc.

[0065] Commercially available cyanate ester compounds (b2), phenol novolac type cyanate esters resin (Lonza Japan "PT-30" and "PT-60"), bisphenol type A prepolymer of trimerized cyanate ester resin ("BA-23" manufactured by Lonza Japan Co., Ltd.) 0S", "BA-3000S", "BTP-1000S" and "BTP-6020S" ) etc. may also be used.

[0066] From the viewpoint of improving heat resistance and crack resistance after heat cycle testing, It is preferable that the maleimide compound (b3) has a molecular weight of 10,000 or more and less than 10,000. A maleimide compound (b3) having a relatively low molecular weight and high reactivity and a maleimide compound (b4) having a relatively high molecular weight and a The relatively low reactivity of the radical-reactive non-conjugated carbon-carbon unsaturated bonds derived from the alicyclic structure By combining this copolymer, which is more bonded, the sparse and dense parts of the cross-linked structure can be It is easy to cause cracks, and effectively improves heat resistance and crack resistance after heat cycle testing. It is believed that this was possible.

[0067] The maleimide compound (b3) is a polyfunctional compound obtained by reacting a polyfunctional amine with maleic anhydride. Examples of the polyfunctional amine include isophorone diamine, diamine Cyclohexylmethane-4,4′-diamine, Huntsman Corporation, Jeffamine D-230 and HK-5 have terminally aminated polypropylene glycol structures 11, D-400, XTJ-582, D-2000, XTJ-578, XTJ-509, XTJ-510, T-403, T-5000, terminal aminated ethylene glycol skeleton XTJ-500, XTJ-501, XTJ-502, XTJ-504, XTJ-51 1. XTJ-512 and XTJ-590 are end-amino-terminated polytetramethylene glycol Has XTJ-542, XTJ-533, XTJ-536, XTJ-548, XTJ-5 59 and others.

[0068] As the maleimide compound (b3), 4,4'-diphenylmethane bismaleimide, m- Phenylene bismaleimide, p-phenylene bismaleimide, 2,2-bis[4-(4- Maleimidophenoxy)phenyl]propane, bis-(3-ethyl-5-methyl-4-maleimidophenoxy)phenyl]propane 4-Methyl-1,3-phenylenebismaleimide, N,N' -Ethylenedimaleimide, N,N'-hexamethylenedimaleimide, bis(4-maleimide) dophenyl) ether, bis(4-maleimidophenyl) sulfone, 3,3'-dimethyl -5,5'-diethyl-4,4'-diphenylmethane bismaleimide, bisphenol A Resins that have two maleimide groups in the molecule, such as diphenyl ether bismaleimide, Phenyl aralkyl type maleimide, polyphenylmethane maleimide (CAS NO: 6778 4-74-1, Reaction product of polymer of formaldehyde and aniline with maleic anhydride ), N,N'-(toluene-2,6-diyl)bismaleimide), 4,4'-diphenyl Ether bismaleimide, 4,4'-diphenylsulfone bismaleimide, 1,3-biphenylsulfone Bis(3-maleimidophenoxy)benzene, 1,3-bis(4-maleimidophenoxy) Benzene, N,N'-ethylene bismaleimide, N,N'-trimethylene bismaleimide , N,N'-propylene bismaleimide, N,N'-tetramethylene bismaleimide, N ,N'-Pentamethylenebismaleimide, N,N'-(1,3-pentanediyl)bis( maleimide), N,N'-hexamethylenebismaleimide, N,N'-(1,7-hexamethylene N,N'-(1,8-octanediyl)bismaleimide, N,N'-(1,8-octanediyl)bismaleimide , N,N'-(1,9-butanediyl)bismaleimide, N,N'-(1,10-decanediyl)bismaleimide N,N'-(1,11-undecanediyl)bismaleimide, N,N'-(1,12-dodecanediyl)bismaleimide, N,N'-[(1,4-phenyl N,N'-[(1,2-phenylene)bismethylene]bismaleimide, N,N'-[(1,3-phenylene)bismethylene]bismaleimide, N,N'-[(1,3-phenylene)bismethylene]bismaleimide 1,6'-bismaleimido-(2,2,4-trimethyl)hexane, N,N'-[ (Methylimino)bis(4,1-phenylene)]bismaleimide, N,N'-(2-hydro (1,3-diylbisiminobiscarbonylbisethylene)bismaleimide N,N'-(dithiobisethylene)bismaleimide, N,N'-[hexamethylene N,N'-carbonylbis(1,4 -phenylene)bismaleimide, N,N',N''-[nitrilotris(ethylene)] Trismaleimide, N,N',N''-[nitrilotris(4,1-phenylene)]tris Maleimide, N,N'-[p-phenylenebis(oxy-p-phenylene)]bismaleimide Mido, N,N'-[methylenebis(oxy)bis(2-methyl-1,4-phenylene)] Bismaleimide, N,N'-[methylenebis(oxy-p-phenylene)]bis(maleimide) N,N'-[dimethylsilylenebis[(4,1-phenylene)(1,3,4, -oxadiazole-5,2-diyl)(4,1-phenylene)]]bismaleimide, N ,N'-[(1,3-phenylene)bisoxybis(3,1-phenylene)]bismaleimide mido, 1,1'-[3'-oxospiro[9H-xanthene-9,1'(3'H)-iso Benzofuran]-3,6-diyl]bis(1H-pyrrole-2,5-dione), N,N' -(3,3'-dichlorobiphenyl-4,4'-diyl)bismaleimide, N,N'-( 3,3'-Dimethylbiphenyl-4,4'-diyl)bismaleimide, N,N'-(3, 3'-Dimethoxybiphenyl-4,4'-diyl)bismaleimide, N,N'-[Methyl N,N'-[Methylenebis(2-ethyl-4,1-phenylene)]bismaleimide N,N'-[(2,6-diethyl-4,1-phenylene)]bismaleimide, Bis(2-bromo-6-ethyl-4,1-phenylene)]bismaleimide, N,N'-[ methylenebis(2-methyl-4,1-phenylene)]bismaleimide, N,N'-[Ethyl N,N'-[sulfonylbis(4,1- phenylene)bis(oxy)bis(4,1-phenylene)]bismaleimide, N,N'- [Naphthalene-2,7-diylbis(oxy)bis(4,1-phenylene)]bismaleimide bismaleimide, N,N'-[p-phenylenebis(oxy-p-phenylene)]bismaleimide, N,N'-[(1,3-phenylene)bisoxybis(3,1-phenylene)]bismale Imide, N,N'-(3,6,9-trioxaundecane-1,11-diyl)bismaleimide Imide, N,N'-[isopropylidenebis[p-phenyleneoxycarbonyl(m-phenyleneoxycarbonyl) N,N'-[isopropylidenebis[p-phenylene]]bismaleimide, Bismaleimide, N,N'-[isopropylidene Bis[(2,6-dichlorobenzene-4,1-diyl)oxycarbonyl(p-phenylene N,N'-[(phenylimino)bis(4,1-phenylene) ]bismaleimide, N,N'-[azobis(4,1-phenylene)]bismaleimide, N ,N'-[1,3,4-oxadiazole-2,5-diylbis(4,1-phenylene) ]bismaleimide, 2,6-bis[4-(maleimido-N-yl)phenoxy]benzo Zonitrile, N,N'-[1,3,4-oxadiazole-2,5-diylbis(3,1 -phenylene)]bismaleimide, N,N'-[bis[9-oxo-9H-9-phosphat (V) -10-oxaphenanthren-9-yl]methylenebis(p-phenylene)]bi Smaleimide, N,N'-[hexafluoroisopropylidenebis[p-phenyleneoxy N,N'-[carbonylbis[( 4,1-phenylene)thio(4,1-phenylene)]]bismaleimide, N,N'-carboxamide Bornylbis(p-phenyleneoxy p-phenylene)bismaleimide, N,N'-[5- tert-Butyl-1,3-phenylenebis[(1,3,4-oxadiazole-5,2 -diyl)(4,1-phenylene)]]bismaleimide, N,N'-[cyclohexylidene N,N'-[methylenebis(oxy)]bismaleimide, N,N'-[methylenebis(oxy) Bis(2-methyl-1,4-phenylene)]bismaleimide, N,N'-[5-[2-[ 5-(Dimethylamino)-1-naphthylsulfonylamino]ethylcarbamoyl]-1, 3-phenylene]bismaleimide, N,N'-(oxybisethylene)bismaleimide, N,N'-[dithiobis(m-phenylene)]bismaleimide, N,N'-(3,6,9 -trioxaundecane-1,11-diyl)bismaleimide, N,N'-(ethylenediamine p-phenylene)bismaleimide, BM from Designer Molecules I-689, BMI-1500, BMI-1700, BMI-3000, BMI-500 0, BMI-9000, ODA-BMI and BAFBMI manufactured by JFE Chemical Co., Ltd. Examples of the functional maleimide include

[0069] When the maleimide compound (b3) is crosslinked by radicals, a radical polymerization initiator Specifically, azo compounds and organic peroxides can be used as the polymerization initiator. One or more types may be used in combination. Azo compounds include 2,2'-azobisisobutyronitrile, 2,2'-azobis (2-Methylbutyronitrile), 1,1'-Azobis(cyclohexane 1-carbonitrile) 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis( 2,4-Dimethyl-4-methoxyvaleronitrile), Dimethyl 2,2'-azobis(2- methylpropionate), 4,4'-azobis(4-cyanovaleric acid), 2,2'- Azobis(2-hydroxymethylpropionitrile), 2,2'-azobis[2-(2- imidazoline-2-yl)propane] can be exemplified. Organic peroxides include benzoyl peroxide, t-butyl perbenzoate, and cumenhydride. diisopropyl peroxydicarbonate, di-n-propyl peroxy Di(2-ethoxyethyl) peroxydicarbonate, t-butyl peroxydicarbonate -Oxy 2-ethylhexanoate, t-Butyl peroxy neodecanoate, t-Butyl peroxypivalate, (3,5,5-trimethylhexanoyl) peroxide, diphenyl Examples include lopionyl peroxide and diacetyl peroxide.

[0070] The allyl group-containing compound (b4) may be either monofunctional or polyfunctional. An example of a polyfunctional allyl compound is (meth)allyl alcohol. Allyl isocyanurate, trimethylolpropane diallyl ether, trimethylolpropane Pantoaryl ether, pentaerythritol diallyl ether, pentaerythritol Triaryl ether, tetraaryloxyethane, polyallyl sucrose, di(meth) ) Allyl phthalate, tri(meth)allyl isocyanurate, tri(meth)allyl cyanurate Other examples include the following compounds: [ka]

[0071] The vinyl group-containing compound (b5) may be monofunctional or polyfunctional. Styrene, vinyltoluene, N-vinylpyrrolidone, N-vinylcaprolactam, vinyl Examples of the polyfunctional vinyl compound include hexane, Diol dinorbornene carboxylate, vinylbenzyl modified polyphenylene ether , pentaerythritol tetranorbornene carboxylate, triethylene glycol Divinyl ether, cyclohexanedimethanol divinyl ether, cyclohexanediamine Examples of the vinyl ethers include vinyl divinyl ether and divinylbenzene. Among these, vinyl group-containing polyphenylene ether is particularly preferred.

[0072] The (meth)acrylate group-containing compound (b6) may be monofunctional or polyfunctional. For example, Monofunctional (meth)acrylamide compounds, polyfunctional (meth)acrylamide compounds, monofunctional ( Examples of the functional (meth)acrylate include polyfunctional (meth)acrylate.

[0073] As monofunctional (meth)acrylamide compounds, diacetone (meth)acrylamide, i Sobutoxymethyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, t-Octyl(meth)acrylamide, N,N-Diethyl(meth)acrylamide, N, N-Dimethylaminopropyl (meth)acrylamide, (meth)acryloylmorpholine , acrylamido-2-methylpropanesulfonic acid, N-isopropyl (meth)acrylic An example is an amide. As a polyfunctional (meth)acrylamide compound, N,N'-diacryloyl-4,7,1 0-Trioxa-1,13-tridecanediamine, N,N',N''-triacryloyl Diethylenetriamine, N,N',N'',N'''-Tetraacryloyltriethylene Tetramine, N,N'-{[2-acrylamide-2-[(3-acrylamidepropoxy bis(methyl)propane-1,3-diyl)bis(oxy)]bis(propane-1,3-di Examples include cyclohexyl)}diacrylamide.

[0074] As monofunctional (meth)acrylates, methyl (meth)acrylate, ethyl (meth)acrylate, Acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyrate (meth)acrylate, isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate ) acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, Lauryl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate (meth)acrylate, isobornyl (meth)acrylate, cyclopentanyl (meth)acrylate acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (Meth)acrylate, benzyl (meth)acrylate, phenol alkylene oxide (Meth)acrylate of alkylene oxide adduct of p-cumylphenol (Meth)acrylate, o-phenylphenol alkylene oxide adduct (meth) Acrylates, (meth)acrylates of nonylphenol alkylene oxide adducts, 2-Methoxyethyl (meth)acrylate, Ethoxyethoxyethyl (meth)acrylate (Meth)acrylates of alkylene oxide adducts of 2-ethylhexyl alcohol , tetrahydrofurfuryl (meth)acrylate, caprolactone-modified tetrahydrofur Furyl (meth)acrylate, (2-ethyl-2-methyl-1,3-dioxolane-4 -yl)methyl (meth)acrylate, (2-isobutyl-2-methyl-1,3-diox solan-4-yl)methyl (meth)acrylate, (1,4-dioxaspiro[4,5] Decane-2-yl)methyl (meth)acrylate, glycidyl (meth)acrylate, 3 ,4-Epoxycyclohexylmethyl (meth)acrylate, (3-Ethyloxetane- 3-yl)methyl (meth)acrylate, 2-(meth)acryloyloxyethyl isocyanate Anate, Allyl (meth)acrylate, N-(meth)acryloyloxyethylhexa Hydrophthalimide, N-(meth)acryloyloxyethyl tetrahydrophthalimide , 2-(meth)acryloyloxyethylhexahydrophthalic acid, 2-(meth)acrylo yloxyethyl succinate, ω-carboxy-polycaprolactone mono(meth)acrylate phosphate, 2-(meth)acryloyloxyethyl acid phosphate, 3-(meth)acryloyloxyethyl acid phosphate Acryloyloxypropyltrimethoxysilane, 3-(meth)acryloyloxypropyl Dimethoxymethylsilane, 3-(meth)acryloyloxypropyltriethoxysilane Examples include 2-(meth)acryloyloxyethyl acid phosphate. In the alkylene oxide adduct, the alkylene oxide is ethylene Examples include propylene oxide and propylene oxide.

[0075] As the polyfunctional (meth)acrylate, a methacrylate group-containing polyphenylene ether, Ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate acrylate, 1,4-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate meth)acrylate, 1,6-hexanediol di(meth)acrylate, 3-methyl-1 ,5-Pentanediol di(meth)acrylate, 2-butyl-2-ethyl-1,3-propanediol dimethacrylate Propanediol di(meth)acrylate and 1,9-nonanediol di(meth)acrylate di(meth)acrylates of aliphatic diols such as acrylates; Cyclohexanedimethylol di(meth)acrylate and tricyclodecanedimethylol Di(meth)acrylates of alicyclic diols such as di(meth)acrylate; Diethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate acrylate, triethylene glycol di(meth)acrylate and tripropylene glycol alkylene glycol di(meth)acrylates such as alkyl di(meth)acrylate; Esterification reaction of neopentyl glycol with hydroxypivalic acid and (meth)acrylic acid The product (hereinafter referred to as "hydroxypivalin acid neopentyl glycol di(meth)acrylate") "), Caprolactone-modified hydroxypivalic acid neopentyl glycol di(methyl p) acrylate; Bisphenols such as di(meth)acrylates of bisphenol A alkylene oxide adducts Di(meth)acrylates of alkylene oxide adducts of alcohol compounds; Hydrogenated bisphenol compounds such as hydrogenated bisphenol A di(meth)acrylate Di(meth)acrylate of substances; Di(meth)acrylate of alkylene oxide adduct of isocyanuric acid, isocyanuric acid Alkylene oxide adduct tri(meth)acrylate, caprolactone modified isocyanate Di(meth)acrylate of alkylene oxide adduct of nuric acid, caprolactone modified iso Isocyanuric acid such as tri(meth)acrylate of alkylene oxide adduct of cyanuric acid Poly(meth)acrylates of alkylene oxide adducts; Trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra( meth)acrylate, pentaerythritol tri- or tetra(meth)acrylate, diphenyl Polyol poly(meth)acrylate such as pentaerythritol penta- or hexa(meth)acrylate Acrylates; Trimethylolpropane alkylene oxide adduct tri(meth)acrylate, dimethacrylate Tetra(meth)acrylate of alkylene oxide adduct of methylolpropane, pentaerythritol Tri- or tetra(meth)acrylate of taerythritol alkylene oxide adduct, Dipentaerythritol alkylene oxide adducts of penta or hexa (meth) acrylic Poly(meth)acrylates of polyol alkylene oxide adducts such as acrylates: Urethane (meth)acrylates; epoxy (meth)acrylates; and An example is polyester (meth)acrylate. In the alkylene oxide adduct, the alkylene oxide is ethylene Examples include propylene oxide and propylene oxide.

[0076] The benzoxazine compound (b7) is a compound having a benzoxazine skeleton. Specifically, o-cresol aniline type benzoxazine resin, m-cresol aniline type Benzoxazine resin, p-cresol aniline type benzoxazine resin, phenol- Aniline-type benzoxazine resin, Phenol-methylamine-type benzoxazine resin, Phenol-cyclohexylamine type benzoxazine resin, phenol-m-toluidin Benzoxazine resin, phenol-3,5-dimethylaniline type benzoxazine Resin, Bisphenol A-aniline type benzoxazine resin, Bisphenol A-amine benzoxazine resin, bisphenol F-aniline type benzoxazine resin, bisphenol F S-aniline type benzoxazine resin, dihydroxydiphenylsulfone-aniline Phosphorus-type benzoxazine resin, dihydroxydiphenyl ether-aniline-type benzoxazine benzoxazine resin, benzophenone-type benzoxazine resin, biphenyl-type benzoxazine resin Fat, Bisphenol AF-aniline type benzoxazine resin, Bisphenol A-methyl Aniline-type benzoxazine resin, phenol-diaminodiphenylmethane-type benzoxazine Sazin resin, triphenylmethane-type benzoxazine resin, and phenolphthalein benzoxazine resins and the like.

[0077] As curable compounds other than the components (b1) to (b7), phenolic resins, isocyanates, etc. Group-containing compounds may also be used.

[0078] 2-2.Other ingredients The composition may further contain other compounds without departing from the spirit of the present disclosure. For example, a copolymer not included in the present copolymer may be used. For the purpose of promoting the crosslinking reaction of radically reactive non-conjugated carbon-carbon unsaturated bonds, A radical polymerization initiator may be added at the same time. Also, the curing process can be efficiently performed by using a catalyst. Suitable examples of such catalysts include imidazole-based, amine-based, and phosphorus-based. An example can be given.

[0079] The radical polymerization initiator may be a known compound. For example, benzoylperoxide may be used. oxide, cumene hydroperoxide, 2,5-dimethylhexane-2,5-dihydro Droperoxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne -3, di-t-butyl peroxide, t-butylcumyl peroxide, α,α'-bi (t-butylperoxy-m-isopropyl)benzene, 2,5-dimethyl-2,5- Di(t-butylperoxy)hexane, dicumyl peroxide, di-t-butylperoxy Peroxyisophthalate, t-butyl peroxybenzoate, 2,2-bis(t-butyl peroxy) 2,2-bis(t-butylperoxy)butane, 2,2-bis(t-butylperoxy)octane, di-t-amylperoxy oxide, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, di(tolyl Trimethylsilyl) peroxide, Trimethylsilyltriphenylsilyl peroxide Examples of peroxides include diisopropylbenzene hydroperoxide and diisopropylbenzene hydroperoxide. ,3-Dimethyl-2,3-diphenylbutane is also suitable as a radical polymerization initiator.

[0080] The amount of the radical polymerization initiator to be added is 0.01 to 10 parts by mass based on 100 parts by mass of the present copolymer. The range of the amount of the carboxylic acid is preferably 0.1 to 8 parts by mass, and more preferably 0.1 to 8 parts by mass. The reaction proceeds smoothly without any damage.

[0081] In addition, inorganic fillers, heat stabilizers, dyes, pigments (e.g., carbon black), polymerization inhibitors agent, defoamer, leveling agent, ion collector, moisturizer, viscosity adjuster, preservative, antibacterial agent, antistatic Examples include anti-blocking agents, UV absorbers, infrared absorbers, and electromagnetic wave shielding agents. Can be obtained.

[0082] The composition may be solvent-free or may contain a solvent. Solvents include toluene, chloroform ... Silene, methyl ethyl ketone, N,N-dimethylformamide, methyl isobutyl ketone , N-methyl-pyrrolidone, acetone, methanol, ethanol, butanol, 2-propanol Alcohol, 2-methoxyethanol, 2-ethoxyethanol, 1-methoxy-2-propanol Propanol, 2-acetoxy-1-methoxypropane, n-hexane, cyclohexane, Examples include cyclohexanone and mixtures thereof.

[0083] From the viewpoint of more effectively achieving a low dielectric constant, it is preferable to use a fluorine-based filler. Fluorine-based fillers include PTFE and PVDF (CF2 and CH2 bonded alternately). (polyvinylidene fluoride with linear structure), Neoflon FEP (tetrafluoroethylene Tetrafluoroethylene-hexafluoropropylene copolymer: Tetrafluoroethylene-hexafluoropropylene copolymer Resin), PFA (Tetrafluoroethylene-Perfluoroalkylvinylether Copolymer) Compound: Perfluoroalkoxy resin), Neoflon ETFE (Tetrafluoroethylene and Ethylene copolymer), ECTFE (polychlorotrifluoroethylene: trifluorochloroethylene Examples include polyethylene resins.

[0084] The type of inorganic filler is not particularly limited. By using an inorganic filler, The crack resistance after the cycling test is improved.

[0085] Specific examples of inorganic fillers include alumina, aluminum hydroxide, and zirconium hydroxide. , barium hydroxide, calcium hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate Nesium, zinc carbonate, barium carbonate, magnesium sulfate, titanium oxide, tin oxide, manium oxide Zinc oxide, magnesium oxide, zirconium oxide, calcium oxide, magnesium oxide, zinc oxide, molybdenum oxide Abdenum, antimony oxide, nickel oxide, calcium silicate, beryllia, calcium titanate Sium, silicon carbide, silicon nitride, aluminum nitride, boron nitride, titanium white, boron Metal compounds such as zinc borate and aluminum borate; talc; clay; mica; glass fibers , kaolin, hydrotalcite, wollastonite, xonotlite, calcium hydrogen phosphate Metal oxides such as calcium phosphate, glass flakes, hydrated glass, and sepiolite and metal nitrides; hydrated metal compounds; fused crushed silica, fused spherical silica, crystalline silica, non-crystalline silica Silica-based materials such as crystalline silica, secondary agglomerated silica, finely divided silica, hollow silica, and porous silica; Examples include nitride-based and carbon-based fillers such as silicon carbide, silicon nitride, titanium carbide, and diamond. It can be shown. Among these, silica, alumina, aluminum nitride, and boron nitride are more preferable. Silica, alumina, and boron nitride are particularly preferred from the viewpoint of effectively increasing crack resistance. .

[0086] 2-3. Properties of resin composition and cured product The composition is cured to obtain a cured product. This means that the material hardens by forming a three-dimensional crosslinked structure through the above process. This refers to a state in which the material has been cured to the extent that the reaction does not proceed. The embodiment in which the curable compound crosslinks the copolymer, the embodiment in which the curable compound crosslinks the copolymer, and the embodiment in which the curable compound crosslinks the copolymer The curing treatment may be carried out in any combination of the above. The reaction is carried out by a radical reaction or the like. Heating may be performed as necessary. When the material is molded into a desired shape, a part of the material may undergo a hardening reaction, but if further hardening treatment is performed, the material will not harden. The term "cured product" does not include the state where some of the components are semi-cured at the resin composition stage. The discharge may be in a B-stage state.

[0087] 3. Manufacturing method of resin composition The composition is obtained by blending the various components. The solid content concentration is, for example, 20 to 60 mass %. The form may be a powder, a film, a sheet, a plate, a pellet, a paste or a liquid. The resin composition in the form of a liquid or paste can be easily obtained by adjusting the viscosity using a solvent. The resin composition in the form of a film, sheet or plate can be, for example, in the form of a liquid or It can be formed by applying a paste-like resin composition and drying it. The pellet-shaped resin composition can be prepared, for example, by crushing the film-shaped resin composition into a desired size. or by dividing it.

[0088] 4. Resin composition layer, laminated sheet and prepreg The present composition can be suitably used as a resin composition layer. and a resin composition layer formed from the present composition and provided on the substrate. The resin composition layer exhibits excellent adhesion after curing treatment, Suitable for bonding with various materials (resin layers, metal layers, inorganic layers such as ITO, composite layers, etc.) For example, adhesive sheets for copper clad laminates (CCL), electronic circuits It is suitable as a bonding material for connecting components such as a substrate and electronic components.

[0089] For example, a coating solution (varnish) of the present composition containing a solvent is applied to one side of a release film, and then an organic The liquid medium such as the solvent is removed and dried at, for example, 40 to 150° C. to form a resin composition layer ( A laminated sheet having a peelable film is obtained. By laminating the films, a laminated sheet, which is an adhesive sheet with double-sided release film, is obtained. By laminating both sides with release films, surface contamination of the adhesive sheet can be prevented. The adhesive sheet can be separated by peeling off the release film. Either the same or different types of release films can be used. This allows you to vary the peeling force, making it easier to peel off in order. A laminate sheet having an adhesive sheet (resin composition layer) is prepared by applying the coating liquid to a substrate other than the adhesive substrate. You may get it.

[0090] The substrate is polyimide film, polyethylene film, polycarbonate, polyethylene Resin materials such as polyimide, liquid crystal polymer, phenolic resin, and aramid resin; copper, aluminum, Metallic materials such as stainless steel; inorganic materials such as ITO, glass, silicon, silicon carbide and composite materials in which these are arbitrarily combined. The alicyclic structure is present at least in one of the groups or the molecular chain terminals, and the ring contains a non-conjugated C=C bond. By using this copolymer, not only is it excellent in heat resistance to various substrates, but it is also easy to process in molding. Excellent workability.

[0091] Coating methods include, for example, comma coat, knife coat, die coat, and lip coat. , roll coating, curtain coating, bar coating, gravure printing, flexo printing, screen printing For this purpose, a known method such as inkjet printing, dip coating, spray coating, spin coating, etc. can be selected. The thickness of the adhesive sheet after drying is required to ensure sufficient adhesiveness and ease of handling. Therefore, the thickness is preferably 5 to 500 μm, and more preferably 10 to 100 μm. .

[0092] The present composition is a material for forming a prepreg obtained by impregnating a substrate with the present composition. The prepreg can be preferably used as a prepreg, for example, by impregnating a fiber substrate with the present composition. The resin composition is then heated and dried to semi-cure (B-stage) to produce The amount of solids of the resin composition attached to the fiber substrate is determined by the resin composition after drying for the prepreg. The content of the oil composition is preferably 20 to 90% by mass, and more preferably 30 to 80% by mass. and more preferably 40 to 70 mass %. For example, The composition is impregnated or coated on a fiber substrate so that the solid content is 20 to 90% by mass. After that, it is heated and dried for 1 to 30 minutes at a temperature of 40 to 250°C, for example, to semi-harden (to B stage). It can be produced by

[0093] As the fiber substrate, any known material can be used without limitation, but organic fibers, inorganic fibers and gas Examples of organic fibers include polyimide, polyester, and tetrafluoroethylene. Examples of inorganic fibers include ethylene and wholly aromatic polyamide. Examples of inorganic fibers include carbon fibers. Glass fibers include E glass cloth, D glass cloth, S glass cloth, and Q glass cloth. Glass cloth, NE glass cloth, L glass cloth, T glass cloth, spherical glass cloth, low Among these, E-glass is the most suitable from the viewpoint of low thermal expansion coefficient. Glass cloth, T-glass cloth, S-glass cloth, Q-glass cloth and organic fibers are preferred. The fiber base material may be used alone or in combination of two or more kinds.

[0094] The shape of the fiber substrate can be appropriately selected depending on the intended use and performance. Woven fabrics, nonwoven fabrics, rovings, chopped strand mats and surfacing mats Examples of weaving methods for the woven fabric include plain weave, sash weave, and twill weave. The thickness of the fiber substrate can be selected and designed as desired according to the desired characteristics. From the viewpoint of thinning, it is preferable that the thickness is 500 μm or less, and 300 μm or less. Below is more preferable.

[0095] The fiber base material may be treated with a silane coupling agent or the like to bring out the desired properties, if necessary. Surface treatment or mechanical opening treatment may be applied. Corona treatment and press treatment may also be applied. Plasma treatment may be performed. The surface treatment with the silane coupling agent is performed with an amino silane coupling agent. vinyl silane coupling treatment, cationic silane coupling treatment, epoxy Examples include silane coupling treatment.

[0096] The method for impregnating the fiber substrate with the resin composition is not particularly limited. For example, , ethers, acetals, ketones, esters, alcohol esters, ketone acetals Alcohols, ether alcohols, ketone ethers, ketone esters, or es A resin composition in the form of a varnish is prepared using an organic solvent such as terethers, and fibers are immersed in the varnish. A method of immersing the substrate, a method of applying varnish to the fiber substrate or a method of spraying the varnish onto the fiber substrate, For example, a method of laminating both sides of a fiber substrate with a film made of a resin composition is exemplified.

[0097] Furthermore, the resin composition layer formed from the present composition and the cured product layer thereof are It is suitable for use as an insulating layer for packages, underfill material, adhesive material, etc. It is also suitable for use as an assembly material for copper-clad laminates. Also suitable for use as a bonding sheet for forming wiring boards and as a cover coat for flexible substrates. do.

[0098] 5. Manufacturing method of the cured product The composition is cured to obtain a cured product. When a photocurable compound is contained, the composition is cured by a heat curing treatment, or by a light irradiation treatment. For example, The resin composition may be molded into a desired shape such as a sheet, and then cured. A molded product such as a sheet of the resin composition can be easily obtained by applying the resin composition to the substrate and drying the applied resin composition. The curing may be performed before or during molding. It is acceptable to use the cured product after molding. A sheet-shaped cured product is also called a cured layer.

[0099] The temperature for the heat curing treatment may be appropriately selected depending on the type of the curable compound. For example, a method of heat treatment at a temperature of 150 to 300° C. for 30 to 180 minutes can be exemplified. When curing, it is sufficient to irradiate the active light with an intensity sufficient to cure the resin. The composition can be heat-pressurized (for example, at 2 MPa) by curing. As a result, a three-dimensionally crosslinked cured product is obtained.

[0100] 6. Cured product and substrate with cured product The cured product obtained from this composition has excellent heat resistance and crack resistance after heat cycle testing. It has excellent resistance to cracking and is also suitable for substrate processing during the manufacturing process, making it suitable for use in metal-clad laminates, printed wiring It is suitable for use as a cured product for various parts including plates, or as a substrate with a cured product that includes this cured product. be.

[0101] A metal-clad laminate can be produced, for example, by forming an insulating layer using the composition, and laminating the insulating layer and a metal layer. The insulating layer can be obtained through a process such as the step of forming an adhesive sheet or a plate from the composition. For example, a prepreg formed using a metal layer and the present composition is preferably used. After lamination, a hardening process is carried out by thermocompression to obtain a metal-clad laminate. The thermocompression step can be carried out by a known method. For example, the thermocompression step can be carried out at a temperature of 120 to 250° C. for 0.5 to 10 minutes. This is done by heat pressing at a pressure of 10 MPa for 0.5 to 5 hours.

[0102] The laminate structure of metal-clad laminates is a two-layer laminate of a metal layer / hardening layer, a metal layer / hardening layer / A laminate consisting of multiple layers of metal layers, or an alternating layer of metal layer / hardened layer / metal layer / hardened layer / metal layer, etc. A metal-clad laminate having a multi-layer structure in which the metal-clad laminate is laminated on the substrate can be exemplified. An insulating layer other than the hardening layer may be included in the laminate. Alternatively, multiple sheets of prepreg or the like may be laminated and cured. It may be possible.

[0103] For example, a circuit pattern is formed on the metal layer of a metal-clad laminate having a layer structure of a metal layer / hardened layer / metal layer. By forming a cured layer, a circuit board having a circuit pattern layer can be obtained. In the case of the build-up on the core substrate, through holes or vias may be formed by using a laser or the like. The process may involve multiple layers of insulating cured layers to form vias. The plate is made by, for example, subtractively bonding the metal layer of a metal-clad laminate to a desired circuit pattern. The desired circuit pattern is formed on one or both sides of the insulating layer by the additive method. It can be obtained by forming

[0104] Copper foil is used as the metal layer. In copper-clad laminates, the copper foil surface is electrolytically plated with copper. After removing the resist layer, there is a process of etching with an alkaline plating solution. The composition has excellent suitability for substrate processing, such as resistance to plating solutions, and is therefore suitable for use in copper-clad laminates. The cured product has excellent crack resistance and heat resistance after a heat cycle test. The substrate with the cured material formed by curing the above can be used for a wide range of purposes in a variety of environments. do.

[0105] For example, the printed wiring board is formed by processing the copper foil of a copper-clad laminate by etching or the like. The substrate on which the signal circuits etc. are formed is attached to a cover film via an adhesive sheet, and then a hardened film is formed. It can be manufactured through a chemical treatment process. For example, a conductor is formed on an insulating flexible film. The process includes forming a pattern, forming a protective film on the pattern via the adhesive sheet, and then performing heat-pressing. A flexible printed wiring board can be manufactured through the above-mentioned process. Examples of the conductive pattern include polyester, polyimide, liquid crystal polymer, and PTFE film. Examples of the method include a method of forming the film by printing technology, and a method of forming the film by sputtering and plating. Cut.

[0106] The cured layer of the composition formed on one or both sides of a printed wiring board is subjected to drilling or other processing. Alternatively, openings may be provided by laser processing or the like, and then filled with a conductive material to form vias. In addition, a circuit layer can be formed on the cured layer of the present composition. The composition has excellent liquid resistance and is therefore suitable for the manufacture of multi-layer printed wiring boards. The printed wiring board has excellent processability, and the heat resistance and the cladding after heat cycle testing are excellent. It has excellent resistance to shock and is therefore suitable for use in various electronic devices such as smartphones and tablet terminals. .

[0107] Since the copolymer has excellent electrical insulation properties, the composition can be further modified by adding an insulating curable compound. For example, the insulating layer forming material (platinum) on the circuit board can be Coverlay layers for printed wiring boards, interlayer insulation layers for built-up boards, bonding sheets, etc. In addition, it is preferably used as a filler such as a thermally conductive filler. By using conductive materials, it is possible to use it as a conductive member of electronic parts. The components include, for example, power semiconductor devices, LEDs, inverter devices, and other power modules. An example can be given.

[0108] Furthermore, by blending an inorganic filler, such as a thermally conductive filler, into the cured product of the present composition, For example, the moldability of the resin composition can be utilized to produce a resin composition having a high heat dissipation property. In particular, it can be used to make heat dissipation parts of a desired shape. Electronic devices that cannot be fitted with fans or heat sinks (smartphones, tablets, etc.) This composition is useful as a heat-dissipating adhesive or heat-dissipating sheet for exterior materials for ponds. It is suitable as an adhesive layer between a heat generating element and a heat sink, or as a heat spreader. The laminate can be used as a heat dissipation layer that covers one or more electronic components mounted on a substrate.

[0109] The amount of this copolymer to be blended is arbitrary, but it is effective in improving the heat resistance of the cured product and in the heat cycle test. In order to improve the crack resistance after the test, the non-volatile content (solid content) of the composition is 10 It is preferable that the content is 1 to 50% by mass with respect to 0% by mass. The range is 4 to 44% by mass. is more preferable, and 6 to 38 mass % is even more preferable. EXAMPLES

[0110] The present disclosure will be described in more detail below with reference to examples. The present disclosure is not limited to the following examples. Unless otherwise specified, "%" and "parts" are based on mass.

[0111] 7.Measurement method 7-1. Measurement of acid anhydride value Approximately 1 g of sample (resin from each synthesis example) was precisely weighed and placed in a stoppered Erlenmeyer flask. The amount of octyl alcohol was more than the amount of acid anhydride groups in the sample. A mixture of amine, 1,4-dioxane, and water (mass ratio: 1.49 / 800 / 80) was Add 10 mL of octylamine and stir for 15 minutes to react with the acid anhydride group. was titrated with a mixture of 0.02M perchloric acid and 1,4-dioxane. A mixture of octylamine, 1,4-dioxane, and water (mass ratio is 1.49) A blank measurement was also performed using 10 mL of (800 / 80). The acid anhydride value was calculated using the following formula: (unit: mgKOH / g) Acid anhydride value (mgKOH / g) = 0.02 x (BA) x F x 56.11 / S B: Blank titration volume (mL) A: titration volume of sample (mL) S: Amount of sample collected (g) F: Potency of 0.02 mol / L perchloric acid

[0112] 7-2. Measurement of amine value Approximately 1 g of sample (resin from each synthesis example) was precisely weighed and placed in a stoppered Erlenmeyer flask, and then 100 mL of non-solvent was added to dissolve the solution. 0.20 g of methyl orange was distilled separately. Dissolve 0.28g of Xylene Cyanol FF in 50mL of water and 0.28g of Xylene Cyanol FF in 50mL of methanol. A few drops of the indicator prepared by mixing the solution was added and held for 30 seconds. After that, the solution The solution was titrated with 0.1N alcoholic hydrochloric acid until it turned blue-gray. The amine value was calculated using the following formula: I did. Amine number (mgKOH / g) = (5.611 x a x F) / S however, S: Amount of sample collected (g) a: Consumption of 0.1N alcoholic hydrochloric acid solution (mL) F: Potency of 0.1N alcoholic hydrochloric acid solution

[0113] 7-3. Measurement of weight average molecular weight (Mw) The Mw was measured using a Showa Denko GPC (gel permeation chromatography) The solvent was THF (tetrahydrofuran), and the column was KF -805L" (Showa Denko Co., Ltd.: GPC column: 8 mm ID x 300 mm size) in series. Two connected tubes were used. Sample concentration: 1% by mass, flow rate: 1.0 mL / min, pressure: 3.8 M The data was calculated using polystyrene equivalents. The analysis uses the manufacturer's built-in software to calculate the calibration curve, molecular weight, and peak area, and retention time. The Mw was calculated for the analysis range of 17.9 to 30.0 minutes.

[0114] 7-4. Non-conjugated carbon-carbon unsaturated bond valence of (i) and (ii) for radical reactivity The radically reactive non-conjugated carbon-carbon unsaturated bond valences of (i) and (ii) are The design values ​​of the raw materials used in the synthesis of this copolymer were calculated. The non-conjugated carbon-carbon unsaturated bonds of (i) and (ii) in terms of the amount of The amount of the compound bound by the bond was calculated from the amount of the compound charged.

[0115] 7-5. Calculation of total functional value The acid anhydride group value, the amine value, and the radical reactive non-conjugated carbon-carbon groups (i) to (ii) The sum of the unsaturated bond values ​​(mgKOH / g) was taken as the total functional value.

[0116] 8. Synthesis of the Copolymer [Synthesis Example 1] LICOCENE PP 1602 (Polypropylene-polyethylene copolymer, (Clariant), M 48 parts of 57000 (W57000, St00%) was dissolved in 50 parts of xylene, and maleic anhydride was obtained as the acid anhydride. 20 parts of carboxylic acid, Luperox DTA (di-t-amyl peroxide, 1.7 parts of Arkema Yoshitomi Co., Ltd. was added and the mixture was stirred for 2 hours while refluxing at 140°C. The point is the peak (1711 cm ) derived from the carboxyl group by FT-IR. -1 (nearby) The maleic anhydride-modified polyethylene polypropylene copolymer was obtained. 1010 (Pentaerythritol tetrakis 3-(3,5-di-tert-butyl-4-hydro Add 0.5 parts of (oxyphenyl)propionate (Kuo Ching Chemical Co., Ltd.) and heat the mixture to 1 00°C, 2.8 parts of 5-norbornene-2-methylamine, dimethylbenzene as a catalyst, Add 0.08 parts of diamine and stir at 100°C for 2 hours. The imidization was carried out by stirring at 170°C for 2 hours while azeotropically distilling water. FT-IR revealed a peak due to the carboxyl group (1711 cm -1 (near the imide group) (1704cm -1 The peak due to alkanes (1397 cm -1 Nearby The reaction was confirmed by the formation of toluene (200 parts) and then diluted with methanol (225 parts). The precipitate was collected by filtration and then diluted with toluene for 20 minutes. 0 parts of ethanol was added to dissolve the mixture, and 225 parts of methanol was added to obtain a precipitate. The product was collected and dried in a vacuum oven at 100°C for 2 hours to remove non-conjugated carbon-carbon bonds in the side chains. A resin with saturated bonds was obtained. The radical reactive carbon-carbon unsaturated bond valence was 10 mg KO H / g.

[0117] [Synthesis Examples 2-8] Copolymerization was carried out in the same manner as in Synthesis Example 1, except that the monomers and their amounts were changed to those shown in Table 1. Synthesis examples 2 to 8 of the combination were obtained.

[0118] [Comparative Synthesis Example 1] 48 parts of LICOCENE PP 1602 was dissolved in 50 parts of xylene to obtain maleic anhydride as the acid anhydride. Add 20 parts of ethyl acetate and 1.7 parts of Luperox DTA as a radical initiator and reflux at 140°C. The mixture was stirred for 2 hours. Then, 200 parts of toluene was added to dilute the mixture, and 225 parts of methanol was added. The precipitate was collected by filtration and then diluted with toluene for 200 mL. The mixture was dissolved in 225 parts of methanol, and the precipitate was obtained by adding 225 parts of methanol. The resin was then collected and dried in a vacuum oven at 100°C for 2 hours to obtain a resin with an acid anhydride group in the side chain. The anhydride value was 10 mg KOH / g.

[0119] [Comparative Synthesis Examples 2-7] The same method as in Comparative Synthesis Example 1 was used, except that the monomers and their amounts were changed to those shown in Table 1. Comparative synthesis examples 2 to 7 of copolymers were obtained.

[0120] The abbreviations in Table 1 are as follows: (Resin before modification) R-1: Polypropylene (LICOCENE PP 1602, Mw57,000, St 0%) R-2: Hydrogenated styrene-butadiene rubber (Dynaron 2324P, Mw 170,000, St 16%) R-3:SEP(G1702, Mw150,000, St28%) R-4:SEBS(G1652, Mw72,000, St30%) R-5: SEBSS (A1536, Mw130,000, St40%) (Compounds containing non-conjugated carbon-carbon unsaturated bonds) T-1: 5-Norbornene-2-methylamine T-2: N-(4-aminophenyl)maleimide

[0121] FIG. 1 shows IR spectrum diagrams of Resin R-5 before modification, Comparative Synthesis Example 5, and Synthesis Example 5. As shown in the figure, in Comparative Synthesis Example 5, a peak derived from a carboxy group (1711 cm -1 On the other hand, in Synthesis Example 5, a peak (around 17 11cm -1 The peak (around 1704 cm ) is due to the C=O of the imide group. -1 Shift to In addition, it was confirmed that the peak due to alkanes (1397 cm -1 Nearby) was confirmed. .

[0122] [Table 1]

[0123] 9. Preparation of resin composition (varnish) [Example 1] The copolymer (P1) of Synthesis Example 1 was used in an amount of 100 parts in terms of solid content, and the initiator (C)-1 was used in an amount of 1 The mixture was placed in a container and mixed with a mixed solvent (toluene: MEK = 1) until the non-volatile content was 25%. :1 (mass ratio) was added and stirred for 10 minutes with a disperser to prepare the varnish of Example 1. .

[0124] [Examples 2 to 31, Comparative Examples 1 to 22] The same method as in Example 1 was used except that the ingredients and amounts were changed to those shown in Tables 2 and 3. Varnishes according to Examples 2 to 31 and Comparative Examples 1 to 22 were prepared.

[0125] The materials used in the examples and comparative examples are shown below. (curable compound) (B)-1: Epoxy compound (b1), XD-1000 (manufactured by Nippon Kayaku Co., Ltd., dicyclopentadiene Diene type epoxy, multifunctional, functional group equivalent weight 252g / eq) (B)-2: Cyanate ester compound (b2), BAD (Mitsubishi Gas Chemical Company, Ltd., Bisphenol A) Nol A type cyanate ester, bifunctional, functional group equivalent weight 139g / eq, molecular weight 278) (B)-3: Maleimide compound (b3), BMI-4000 manufactured by Yamato Chemical Industry Co., Ltd., bisphenol Nol A Diphenyl Ether Bismaleimide, 2-functional, functional group equivalent weight 285.3g / e q, molecular weight 570.6) (B)-4: Allyl group-containing compound (b4), Taiku (manufactured by Shinryo Corporation, triallyl isocyanurate) ester, trifunctional, molecular weight 249.3) (B)-5: Vinyl group-containing compound (b5), OPE-2St 1200 (Mitsubishi Gas Chemical Co., Ltd. Vinylbenzyl modified polyphenylene ether, bifunctional, functional group equivalent: 590g / eq , number average molecular weight 1180) (B)-6: (meth)acrylate group-containing compound (b6), Noryl SA9000 (manufactured by SABIC, Methacrylate-containing polyphenylene ether, bifunctional, functional group equivalent: 850g / eq , number average molecular weight 1700) (B)-7: Benzoxazine compound (b7), 3,3'-(methylene-1,4-diphenyl Benzoxazine) (Shikoku Chemical Industry Co., Ltd.) Co., Ltd., Pd-type benzoxazine), bifunctional, oxazine equivalent 217) (Initiator (C)) (C)-1: Radical initiator (c1), Parmicle D (manufactured by NOF Corp., dicumyl peroxide) , molecular weight 270.4) (C)-2: Epoxy initiator (c2), TETRAD-X (manufactured by Mitsubishi Gas Chemical Company, Inc., multifunctional epoxy initiator) epoxy resin, molecular weight 360.5) The epoxy initiator (c2) has an epoxy group, which is the same as the epoxy compound (b 1) can be classified into 2), but in this example, the initiator that opens the epoxy ring by the amine structure is mainly used. Since it is used as an initiator, it is classified as an initiator (C). (Filler (D)) (D)-1: SO-C2 (average particle size 0.4 to 0.6 μm, manufactured by Admatechs Co., Ltd., silica ) (D)-2: AO-509 (average particle size 7 to 13 μm, manufactured by Admatechs, alumina) (D)-3: SP-2 (average particle size D50 4 μm, manufactured by Denka, boron nitride) (D)-4: HF-01 (average particle size D50 1.1 μm, manufactured by Tokuyama Corporation, nitrided aluminum) (Olefin Polymer (E) Containing a Radical-Reactive Carbon-Carbon Unsaturated Bond in the Side Chain) (E)-1: Styrene-butadiene-styrene resin (Tufprene 126S, Asahi Kasei Corporation) Company) (E)-2: Polybutadiene resin (PB B-3000, manufactured by Nippon Soda Co., Ltd.)

[0126] 10. Preparation of evaluation samples 10-1. Preparation of adhesive sheet The resin varnish of each example was applied using a doctor blade so that the thickness after drying was 50 μm. A 50μm thick heavy-duty release film (polyethylene terephthalate coated with a heavy-duty release agent) was applied to the The mixture was evenly coated on a polyethylene terephthalate (PET) film and dried at 100°C for 2 minutes. The adhesive sheet was then cooled to room temperature to obtain a single-sided release film-attached adhesive sheet. The adhesive sheet surface of the film-attached adhesive sheet is covered with a 50 μm thick light release film (coated with a light release agent). A heavy-duty peel-off film is then applied to the polyethylene terephthalate (PET) film. Thus, an adhesive sheet with double-sided release films was obtained, which consisted of a film / adhesive sheet / light release film.

[0127] 10-2. Manufacturing of copper-clad laminates The light release film was peeled off from the adhesive sheet with double-sided release film obtained by the above method, and the exposed The adhesive sheet surface is laminated with a 50 μm polyimide film and a 12 μm copper foil. A vacuum laminator (a small pressure type vacuum laminator manufactured by Nichigo Morton Co., Ltd.) was placed on the copper foil side of the single-sided copper-clad laminate. The vacuum lamination conditions were heating temperature 100°C, The vacuum time was 60 seconds, the ultimate vacuum pressure was 2 hPa, the pressure was 0.4 MPa, and the pressurization time was 60 seconds. Next, peel off the heavy-duty release film and place a second single-sided copper-clad laminate on the exposed adhesive sheet. The polyimide side of the laminate was then temporarily bonded using a vacuum laminator, and then heated to 200°C in a vacuum heat press. The adhesive sheet was thermally cured at 2 MPa for 2 hours, and the polyimide film / copper foil / adhesive sheet was A sample for evaluation was prepared with a laminated structure of cured resin / polyimide film / copper foil film. did.

[0128] 11. Evaluation α. Heat resistance The copper-clad laminates prepared in each example were cut to a width of 10 mm and a length of 65 mm, and then used as test pieces. After storing them under various conditions, the copper foil surface was brought into contact with molten solder at various temperatures and left floating for 1 minute. After that, the appearance of the test piece was visually observed, and the adhesive layer after curing was checked for any signs of adhesion such as foaming, lifting, or peeling. The test was conducted to evaluate the thermal stability of the adhesive layer after curing when soldering. The evaluation is based on appearance. Good heat resistance does not change in appearance, whereas poor heat resistance The poor quality of the soldering results in bubbles and peeling after soldering. The results are judged based on the following criteria: I refused. AA: After storing for 24 hours in an atmosphere of 85°C and 85% relative humidity, float it on molten solder at 300°C. No change in appearance. A: Does not satisfy the above AA requirements. After storing for 24 hours in an atmosphere of 40°C and 90% humidity, the material melts at 300°C. The appearance does not change even when floating in solder. B: Does not satisfy A above. The test piece was stored for 24 hours in an atmosphere of 40°C and 90% humidity. No change in appearance when placed in molten solder at ℃. C: Does not satisfy A and B above. The test piece was stored for 24 hours in an atmosphere of 23°C and 50% humidity. No change in appearance when placed in molten solder at 80℃. D: Does not satisfy A to C above. The test piece was stored for 24 hours in an atmosphere of 23°C and 50% humidity. No change in appearance when floated in molten solder at 60℃. E: Does not satisfy A to D above. The test piece was stored for 24 hours in an atmosphere of 23°C and 50% humidity. No change in appearance when placed in molten solder at 40°C. F: A test piece stored for 24 hours in an atmosphere of 23°C and 50% humidity is floated in molten solder at 240°C. The appearance changes when the product is heated, which is problematic in practical use.

[0129] β. Dielectric properties Place the adhesive sheet with double-sided release film in an atmosphere of 23°C and 50% relative humidity for at least 24 hours. After storage, the release film was removed and the samples were measured under the same temperature and humidity conditions using an A.E.T. dielectric constant measuring device. The dielectric loss tangent (Df) at a measurement frequency of 10 GHz was calculated using the cavity resonator method. Ta. AA: Df is less than 0.0004 A: Df is greater than or equal to 0.0004 and less than 0.0005 B: Df is 0.0005 or more and less than 0.0010 C: Df is greater than or equal to 0.0010 and less than 0.0020 D: Df is greater than or equal to 0.0020 and less than 0.0030 E: Df is greater than or equal to 0.0030 and less than 0.0035 F: Df is 0.0035 or more. There is a problem in practical use.

[0130] γ. Stress relaxation (crack resistance) characteristic evaluation The L / S ratio is 25μm / 25μm, and the copper thickness is 25μm and 50μm, respectively. A glass cloth-based epoxy resin copper-clad laminate with a wiring pattern is prepared as an inner layer circuit board. On both sides of the laminate, the resin sheets of each example prepared by the above-mentioned method were applied at 200° C. and 3.0 MPa. Then, the board was vacuum-heated and pressed for 2 hours, and finally, copper foil was placed on the outermost layers on both sides for evaluation. A printed wiring board was obtained. The evaluation printed circuit board was then subjected to a thermal shock test using a thermal shock device (TSE-11-A, Espec Corporation). The specimens were placed in a container made of 125℃ for 15 minutes and exposed to high temperature conditions of 125℃ for 15 minutes and low temperature conditions of -50℃ for 15 minutes. The printed wiring board for evaluation was cut and the exposed cross section was scanned. The presence or absence of cracks was observed at a magnification of 5000 times using a scanning electron microscope (SEM). A crack is defined as a crack with a size of 0.1 μm or more. The evaluation criteria are as follows: do. AA: No cracks were observed after 4000 heat cycle tests. This is a very good result. do. A: Does not satisfy the above AA criteria. No cracks were observed after 3,000 heat cycle tests. This is an extremely good result. B: Does not satisfy A above. No cracks were observed after 1000 heat cycle tests. This is a very good result. C: Does not satisfy A and B above. No cracks occur after 200 heat cycle tests. . Good results. D: Does not satisfy A to C above. No cracks occur after 100 heat cycle tests. There are problems in practical use. E: Cracks occur before 100 cycles of testing. Problematic for practical use.

[0131] [Table 2] [Table 3]

Claims

1. The main chain is a structural unit derived from a conjugated diene compound and / or an alicyclic or linear non-conjugated olefin. A modified olefin copolymer containing a structural unit derived from an olefin compound, Monocyclic and / or polycyclic structures in at least one of the side groups, side chains and molecular chain terminals It has a structure, The ring of the monocyclic structure and / or any ring of the polycyclic structure consists of carbon atoms. At least one of an alicyclic skeleton and an alicyclic skeleton consisting of carbon atoms and hetero atoms and a modified olefin-based copolyester that satisfies at least one of the following (i) and (ii): Polymer. (i) The alicyclic skeleton has a radical-reactive non-conjugated carbon-carbon unsaturated bond. (ii) a carbon atom constituting the alicyclic skeleton and a ring constituting the ring bonded to the carbon atom The free carbon atoms are connected to each other by radically reactive non-conjugated carbon-carbon unsaturated bonds.

2. 2. The modified polymer according to claim 1, wherein the main chain is substantially free of unsaturated bonds except at the molecular chain terminals. Olefin copolymer.

3. The modified olefin according to claim 1, wherein the main chain contains a structural unit derived from an aromatic vinyl compound. Copolymer.

4. A block consisting of structural units derived from aromatic vinyl compounds and a block consisting of structural units derived from conjugated diene compounds. The modified olefin copolymer according to claim 1 , comprising a block containing a unit.

5. The block containing the structural unit derived from the conjugated diene compound may further contain a structural unit derived from an aromatic vinyl compound. The modified olefin copolymer according to claim 3, comprising the following structural units:

6. It is a hydrogenated styrene-based elastomer. Styrene-ethylene butylene block copolymer (SEB), styrene-ethylene butylene block copolymer styrene-ethylene-butylene-styrene block copolymer (SEP), copolymer (SEBS), styrene-ethylene propylene-styrene block copolymer (SEPS), styrene-ethylene-butylene-styrene-styrene block copolymer ( SEBSS), styrene-isobutylene-styrene block copolymer (SIBS), and and styrene-ethylene-ethylene propylene styrene block copolymer (SEEPS) 2. The modified olefin copolymer according to claim 1, which is a modified product of any one of the above.

7. A resin composition comprising the modified olefin copolymer according to claim 1.

8. The curable compound further comprises an epoxy compound (b1), a cyanate compound (b2), and a cyclic alkylene oxide (c1). a maleimide compound (b3), an allyl group-containing compound (b4), Vinyl group-containing compound (b5) and (meth)acrylate group-containing compound (b6), benzo The resin composition according to claim 7, further comprising at least one selected from the group consisting of oxazine compounds (b7). Composition.

9. The resin composition according to claim 7, further comprising an inorganic filler.

10. A substrate and a resin composition according to any one of claims 7 to 9 formed on the substrate. and a resin composition layer formed by the above-mentioned method.

11. A prepreg comprising a substrate impregnated with the resin composition according to any one of claims 7 to 9.

12. A cured product obtained from the resin composition according to any one of claims 7 to 9.

13. A cured product formed by curing the resin composition according to any one of claims 7 to 9. Board with objects attached.

14. An electronic device comprising the substrate with the cured product according to claim 13.

Citation Information

Patent Citations

  • Thermoplastic elastomer

    JP2006131663A

  • Resin composition, prepreg, laminated plate, multilayer printed wiring board and semiconductor package

    JP2020169276A

  • Thermosetting cyclic imide resin composition

    JP2022111423A

  • Thermoplastic elastomer composition and method for preparing same

    WO2017047274A1